Beyond gastroenteritis: first evidence of systemic biochemical disturbances, predominantly coagulation dysfunction, in Neoboletus poisoning - Jia Li; Yuan-Tian Lu; Xiu-Juan Li; Ming Li; Ping Wei; Tai-Jie Yu; Yu-Xian Gao; Ting Li; Yuan-Yuan Xiong; Yi Liu; Li-Ping Tang (Toxicon, 2026)

Acute liver injury and facial edema following ingestion of mushroom Descolea quercina - Ting Li; Xiu-Juan Li; Tai-Jie Yu; Wen-Hao Zhang; Yuan-Tian Lu; Yu-Xian Gao; Yuan-Yuan Xiong; Jun Gao; Yi Liu; Li-Ping Tang (Toxicon, 2026)

Qianlong Shutong Formula alleviates benign prostatic hyperplasia associated with the regulation of inflammation, fibrosis and the Hippo-YAP/TAZ pathway - Ze-chao Zhang; Xue-jin Ye; Chang-jie Shang; Zhi-feng Wei; Yu Chen; Shu-ping Huang; Min Zhu; Bo-tao Tang; Tai-sheng Liang (Tissue and Cell, 2026)

Chronic exposure to chlorate at regulatory safety limits induces p21/p16-mediated neuronal senescence and Parkinsonian-like decline - Cai-Jhen Wu; Chien-Tai Hong; Jiun-Lin Horng; Hung-Shao Lai; Hao-Yu Tsai; Tsorng-Harn Fong; Chen-Yuan Hsiao; Cheng-Ying Chu; Yvonne Jing Mei Liew; Tien-Chun Yang (Environmental Pollution, 2026)

Novel D-A1-A2-π-A self-assembled monolayer in suppressing the Voc deficit of the wide-bandgap perovskite solar cells - Dong-Tai Wu; Yu Hsuan Lin; Yi-Chen Lin; Hsin Li; Yu-Chen Liang; Yu-Tong Hung; Yi-Sheng Lin; Wei-Jia Qiu; Shi-Chun Liu; Yuan Jay Chang; Chieh-Ting Lin (Chemical Engineering Journal, 2026)

Identification and functional validation of a beta-amyrin synthase for Clinopodiside A biosynthesis in medicinal plant Clinopodium chinense - Qianlan Liu; Chun Liu; Zitong Tan; Yu Fu; Ting He; Yi Yuan; Yuling Tai (Plant Science, 2026)

Engineered aptamer-confined hydrogel for label-free detection of heavy-metal ions with enhanced interference tolerance - Long Bai; Xiuxiu Wu; Lei Huang; Haohao Chen; Jinsong Yu; Ziqing Ye; Min Yuan; Hui Cao; Liling Hao; Fengqin Yin; Tai Ye; Fei Xu (Food Chemistry, 2026)

A dual-function electroactive hydrogel platform for mitigating oxidative stress and restoring muscle function - Yi Lin; Zi-Hao Lin; Hai-Bin Jiang; Yu-Hao Kang; Qing-Song Deng; Rong-Tai Zuo; Zhi-Qi Lin; Er-Peng Yang; Jun-Jie Xu; Clara Chen; Xi-Ming Wang; Jin-Zhong Zhao (Chemical Engineering Journal, 2026)

Extreme drought converts grassland carbon sinks to sources in Inner Mongolia, but strong recovery follows: Insights from a 9-year study - Shaoling Li; Rongle Zhang; Juejie Yang; Tai Yang; Cong Wang; Frank Hagedorn; Arthur Gessler; Marcus Schaub; Fei Li; Shikui Dong; Qiang Yu (Agricultural and Forest Meteorology, 2026)

Towards eco-friendly biofuel design: Atmospheric transformation and divergent ecological risk assessment of dimethylbutanol isomers - Zhi-Meng Wang; Wan-Ying Yu; Shuang Ni; Tai-Xing Chi; Feng-Yang Bai; Ke Zhang; Xiu-Hui Zhang; Zhen Zhao (Journal of Cleaner Production, 2026)

Improving the flavor and quality of roasted mackerel (Pneumatophorus japonicus) via sous-vide cooking: Tracking the dynamics of key volatile compounds - Hui Liu; Tai-yu Li; Wei-yi Xu; Yong-jie Long; Yan-wei Yuan; Jing-jing Fu; Jian-zhong Han; Yue-wen Chen; Wen-qiang Cai (Food Chemistry, 2026)

Photothermal-photodynamic enhanced antibacterial activity of PDA-ALA nanoparticles enables dual-light-responsive sweet cherry preservation - Jianzhuo Du; Tai Gao; Jialin Wang; Pingyu Ge; Haoyang Du; Yu Tong; Jiapei Wu; Weizhuo Xu; Shuling Zhang; Xu Zhao (Food Bioscience, 2026)

The lnc40545-miR-965-CYP307A1 regulation pathway mediates imidacloprid resistance in Rhopalosiphum padi (L.) - Yong-Po Lv; Ren-Jie Li; Yu-Tai Jiang; Bai-Zhong Zhang; Yu-Yang Peng; Yong Sun; Dong-Mei Chen; Fan-Bin Kong; Run-Qiang Liu; Hai-Hong Gu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Corrigendum to “Mg-doped CoCr₂O₄ nanoparticles with fast humidity sensing and mixed-controlled pseudocapacitive charge storage” [Chem. Eng. J. 535 (2026) 175200] - K. Manjunatha; Shih-Lung Yu; Yi-En Wu; Ming-Kang Ho; Tsu-En Hsu; Yun-Tai Yu; B. Chethan; Mithun Prakash Ravikumar; Sakar Mohan; Tsung-Te Lin; Yi-Ru Hsu; Meng-Chu Chen; et al. (Chemical Engineering Journal, 2026)

Optimized fast desensitized Kalman filter - Tai-shan Lou; Liang Ma; Li-ying Jiang; Yu-zhao Jiao; Liang-Yu Zhao; Ren-long Qi (Advances in Space Research, 2026)

Two Contributions to the Hypogeous Boletales of China: A Novel Rhizopogon Species and a New National Record of Turmalinea persicina - Jia Li; Chang Xu; Tai‐Jie Yu; Wen‐Hao Zhang; Xiu‐Juan Li; Yu‐Xian Gao; Yuan‐Tian Lu; Li‐Ping Tang (New Zealand Journal of Botany, 2026)
Hypogeous Boletales are ectomycorrhizal fungi with sequestered hymenophores; some species are ecologically valuable as edible mushrooms. Despite their ecological and economical importance, the diversity of this group in China remains poorly understood. In this study, we performed phylogenetic analyses based on four loci (ITS, LSU, TEF1‐α , and RPB2 ) and detailed morphological examinations of specimens belonging to Rhizopogon (Rhizopogonaceae) and Turmalinea (Boletaceae). We describe and illustrate R. sinoevadens , a new species from China, and report the first Chinese record of T. persicina , a species originally described from Japan. These discoveries underscore the previously underestimated diversity of hypogeous Boletales in China and provide a foundation for future taxonomic and ecological studies.

Primary amine-functionalized HTO/CMC/PVA composite films: Highly selective lithium adsorption and applications in complex lithium-containing systems - Shengkai Liu; Ruimeng Liu; Wenxuan Wang; Dandan Hu; Yu Han; Cong Li; Huiling Li; Chang Wan; Tai Peng; Wei Wang; Daxin Liang (Process Safety and Environmental Protection, 2026)

Cation-size-directed interfacial and electronic engineering of Ti3C2Tx MXenes via ionic liquid intercalation for high-rate proton storage - Jeremiah Hao Ran Huang; Wei-Siang Lo; Yu-Ting Tai; Yu-Chun Shih; Hong-Kang Tian; I-Wen Peter Chen (Chemical Engineering Journal, 2026)

Advances in Alzheimer’s disease: mechanistic insights and therapeutic targets - Yu-Juan Jia; Yi-Jun Ge; Bowei Li; Ying Yang; Huaqiu Chen; Jie Liu; Jun-Hong Guo; Jin-Tai Yu; Ke-Qiang Ye; Jian-Zhi Wang; Weihong Song; Yan-Jiang Wang (Science China Life Sciences, 2026)

Quantifying the light interception and canopy photosynthesis of strip intercropping system based on 3D canopy photosynthesis model - Si-Rong Huang; Qing-Feng Song; Zheng Guo; Qiu-Feng Long; Li-Sha Zhang; Yue Li; Yuan Yang; Xiao-Chun Wang; Feng Yang; Tai-Wen Yong; Jiang Liu; Yan-Hong Yan; et al. (Computers and Electronics in Agriculture, 2026)

Corrigendum to <‘Circulating exosome-mediated AMPKα–SIRT1 pathway regulates lipid metabolism disorders in calf hepatocytes’> <[Research in Veterinary Science 169 (2024) /105177]> - Daoliang Zhang; Hongyan Ding; Chang Liu; Yingying Huang; Wenjun Tai; Shibin Feng; Xichun Wang; Chang Zhao; Yu Li (Research in Veterinary Science, 2026)

Tunable thermosensitive-photothermal antibacterial film based on photothermal agent polycaffeic acid for preservation of Scomberomorus niphonius - Jialin Wang; Chenning Zhang; Yu Tong; Pingyu Ge; Jianzhuo Du; Tai Gao; Weizhuo Xu; Xu Zhao (Food Research International, 2026)

Effects of dietary corn-fermented protein as a sustainable ingredient on growth performance, immune response, and disease resilience in whiteleg shrimp (Litopenaeus vannamei) - Yi-Chun Kuo; Hoang Trieu Quan Tran; Thi Hang Ho; Anant Bharadwaj; Yu-Ting Chu; Tai-Yuan Chen; Fan-Hua Nan; Po-Tsang Lee (Fish & Shellfish Immunology, 2026)

Decoupling crosslinking networks for improved rapid strain response and intelligent sensing applications - Zhiqiang Zhai; Xiaosong Du; Xudong Wang; Zhen Yuan; Qiaochu Guo; Yin Long; Yang Wang; Yanhao Yu; Huiling Tai; Yadong Jiang (Chemical Engineering Journal, 2026)

Efficacy of NEPA for prevention of chemotherapy induced nausea and vomiting in head and neck cancer patients receiving cisplatin-based chemotherapy - Tzer-Zen Hwang; Chih-Chun Wang; Chuan-Chien Yang; Ching-Feng Lien; Chien-Chung Wang; Yu-Chen Shih; Shyh-An Yeh; Tai-Heng Yeh; Meng-Che Hsieh (European Journal of Clinical Pharmacology, 2026)

Endothelial FAM171A2 is required for maintaining autophagy flux and blood–brain barrier integrity - Si-Da Han; Ning Ding; Jia-hui Huang; Yi-Wei Feng; Kai-Min Wu; Shi-Dong Chen; Qiang Dong; Mei Cui; Ting-ting Wang; Peng Yuan; Jin-Tai Yu (Science Bulletin, 2026)

Defect-engineered nitrogen-doped carbon from tannic acid for highly efficient peroxydisulfate activation via nonradical pathways - Rui Luo; Tong Yu; Kexin Tai; Xiaoju Wen; Zongtang Liu; Binbin Qian; Qihui Xu; Haijiao Xie; Xiankun Wu (Journal of Environmental Chemical Engineering, 2026)

Harnessing dual-stable conformers in o-carborane-based multi-resonance emitters for achieving single-emitter white OLEDs - Zezhu Xiao; Chen-Yu Lin; Jianxing Chen; Songqian Ni; Xingtian Wang; Ming-Yu Teng; Weiguo Zhu; Pi-Tai Chou; Xiugang Wu (Chemical Engineering Journal, 2026)

Mg-doped CoCr2O4 nanoparticles with fast humidity sensing and mixed-controlled pseudocapacitive charge storage - K. Manjunatha; Shih-Lung Yu; Yi-En Wu; Ming-Kang Ho; Tsu-En Hsu; Yun-Tai Yu; B. Chethan; Mithun Prakash Ravikumar; Sakar Mohan; Tsung-Te Lin; Yi-Ru Hsu; Meng-Chu Chen; et al. (Chemical Engineering Journal, 2026)

Deletion of the SHORT Syndrome Gene Prkce Results in Brain Atrophy and Cognitive and Motor Behavior Deficits in Mice - Yu-Long Bao; Wei-Peng Duan; Yan Yang; Zhijie Lin; Ying Shen; Rui Zheng; Xin-Tai Wang (Neuroscience Bulletin, 2026)

The emerging role of high-throughput proteomics in advancing precision medicine - Jia You; Yue-Ting Deng; Luo Chen; Lin-Bo Wang; Yu Guo; Ze-Yu Li; Jian-Feng Feng; Jin-Tai Yu; Wei Cheng (Science Bulletin, 2026)

Assessing organic substitution thresholds in smallholder farms: Results from a 34-year experiment on crop—livestock integration systems - Yu Ning; Shuai-lin Li; Xin-hui Zhang; Zhu-qing Xia; Yun Gao; Lu Sun; Qiang Ma; Wan-tai Yu (European Journal of Agronomy, 2026)

Thiourea-based networks with nanocarbon fillers for antistatic, self-healing, and plasma-resistant elastomers - Tse-Yu Lo; Shu-Fan Li; Chia-Wei Chang; Huan-Wei Lin; Heng-Hsuan Su; Kuan-Hung Liu; Po-Chia Huang; Jiun-Tai Chen (Chemical Engineering Journal, 2026)

Profiling of macroelements and microelements in colorectal cancer patients and their clinicopathological characteristics - Gihani Vidanapathirana; Jun Yu Woon; Fentaw Tadese Berhe; Md Sajedul Islam; Neda Moetamedirad; Md. Nurujjaman; Zhuo Chen; Cu Tai Lu; Sujani Kodagoda Gamage; Alfred K. Lam; Vinod Gopalan (BioMetals, 2026)

Impact of chlorine dioxide on zearalenone degradation in corn germ and corn oil quality - Xifan Yu; Bolei Yang; Bowen Tai; Ziying Yan; Zifan Wei; Yuehua Wang; Tiejun Li; Yan Wang; Fuguo Xing (Food Chemistry, 2026)

Intranasal biomimetic vesicle platform reprograms the glioblastoma microenvironment for enhanced immunotherapy - Shuo Li; Chao Qin; Fan-Yu Qian; Jin-Hao Wang; Xiang-Gui Wu; Wen-Qing Li; Tai-Yu Liu; Zhao-Jie Chen; Bei-Yuan Zhang; Qi-Yue Liu; Li-Sha Liu; Li-Fang Yin (Chemical Engineering Journal, 2026)

Development of active packaging films incorporating HP-β-CD encapsulated laurel essential oil for pork preservation - Zhiyuan Tai; Wanzhou Yang; Yuexin Pan; Wenhao Zhang; Mingqian Wang; Zeyuan Yu; Xiaodong Yu; Qiyi He (Food Chemistry, 2026)

An accelerated meshfree computational framework with machine learning classification for multi-phase modeling of landslide - Kuan-Chung Lin; Yih-Chin Tai; Po-Han Lee; Hock-Kiet Wong; Yanran Wang; Yu-Shu Lu; Jiun-Shyan Chen (Computers and Geotechnics, 2026)

Sonofoam: An ultrasound-responsive foam for broad pleural coverage and sonoporation-enhanced drug delivery in pleurodesis - Hsin-Yi Lin; Wei-Chih Liao; Yun-Chieh Lin; Hsin-Chin Li; Min-Yu Tsou; Bo-Tai Cheng; Yu-Nan Huang; Ulziijargal Sukhbat; Chun-Yi Chiang; Chi-Fen Chuang; Zong-Han Hsieh; Chih-Yen Tu; et al. (Chemical Engineering Journal, 2026)

Spatio-temporal dynamics of fish assemblages at an offshore wind farm and a comparison with mature artificial reefs - Kwang Tsao Shao; Ching Han Chang; Ching Yi Chen; Lin Tai Ho; Yi Ta Shao; Hsin-Chieh Chiang; Wei-Ning Lee; Hsien Ju Tsai; Tien-Yu Huang; Chun-Yu Chang (Frontiers in Marine Science, 2026)
Introduction Offshore wind farms (OWFs) are vital for sustainable energy. The underwater foundations of those wind turbines provide a complex structure that creates new habitats and attracts fishes. However, whether OWFs had the same ecological function as purpose-built artificial reef (AR) and how they alter the original fish community remain unclear. Methods To evaluate the spatial and temporal variations in fish assemblages, we conducted a multi-part investigation at the Formosa Wind Farm, located off the coast of Miaoli County, Taiwan. Temporal changes were assessed through SCUBA surveys at turbine foundations in 2017, 2018, and 2025, with the 2025 data allowing for a direct comparison with the nearby existing artificial reefs. To assess spatial effects, pole-and-line surveys were conducted from Apr to Oct in 2024 and 2025 at varying distances from the turbines. Results Our investigation documented 86 species of reef-associated fishes exclusively within 50 m of turbine foundations; none were caught in the surrounding sandy areas or documented in pervious fishery records. The results demonstrated that fish assemblages around the turbine piles changed successively over the years. Although the species composition in 2025 differed between the OWF and the established AR sites, key ecological metrics such as species richness, diversity, and trophic structures showed no significant differences. Discussion These findings demonstrated that the underwater structure of offshore wind turbines can function as AR, creating novel reef habitats and supporting reef-associated fish community within a finite spatial extent. Overall, OWFs may provide ecological benefits in addition to renewable energy, highlighting their potential role in balancing energy development with marine conservation.

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

Melatonin Improves Neuroprotection and Neuroplasticity in Middle-Aged Mice Following Permanent Focal Cerebral Ischemia - Liang-Yi Chen; Shih-Huang Tai; Sheng-Yang Huang; Chih-Chieh Tsao; Yu-Ning Chen; Hao-Hsiang Hsu; Ai-Hua Lee; E.-Jian Lee (Molecular Neurobiology, 2026)

Identification of lncRNAs Associated with Imidacloprid Resistance in the Grain Aphid Rhopalosiphum padi (L.) (Hemiptera: Aphididae) - Ling-Ling Cui; Yong-Po Lv; Ren-Jie Li; Yu-Tai Jiang; Bai-Zhong Zhang; Yu-Yang Peng; Jin-Song Zheng; Fan-Bin Kong; Run-Qiang Liu (Neotropical Entomology, 2025)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Mechanistic differences in ce-MoS2 catalytic activation of peroxides: Pathway divergence and reactive species roles - Shuyun Tai; Lei Sun; Yuxin Wang; Ruolan Huang; Yang Yang; Yu Chen; Hong Chang (Journal of Hazardous Materials, 2025)

Environmental and economic sustainability of wastewater reclamation and reuse in urban areas - Francesca Lucy U. Del Rosario; Jude Nathan T. Montallana; Tai-Yuan Huang; Jhud Mikhail O. Aberilla; Yu-Ming Tu (Journal of Environmental Chemical Engineering, 2025)

Hydrogeochemical characteristics and the monitoring from 2020 to 2023 of hot spring waters in Tatun Volcanic Group, Taiwan - Ju-lien Pi; Hsueh-Yu Lu; Hsiao-Fen Lee; Hung-Chun Chao; Chen-Feng You; Tsung-Ren Peng; Raymond Patrick R. Maximo; Chia-Tai Wu; Ya-Wen Wu; Chung Fang; Cheng-Horng Lin (Journal of Asian Earth Sciences, 2025)

Prenatal exposure to environmental metal mixtures and social development in early childhood: Evidence from a birth cohort and mechanistic study - Susu Wang; Tai Ren; Yun Zhou; Chunping Hu; Xiaogang Yu; Junxia Liu; Xin Liu; Kan Shao; Yuanyuan Li; Chong-Huai Yan; Wei-Guang Li; Fei Li (Environmental Research, 2025)

Trans-anethole enhances mesenchymal stem cell derived exosomes function to inhibit H2O2-induced rheumatoid arthritis-like inflammation in HIG-82 synovial cells - Tai-Lung Huang; Yu-Chun Chang; Wei-Wen Kuo; Shih-Wen Kao; Chia-Hua Kuo; Dennis Jine-Yuan Hsieh; Kuan-Ho Lin; Tsung-Jung Ho; Chih-Yang Huang (Molecular Biology Reports, 2025)

Corrigendum to “the different impacts of ambient air pollution exposure on the risks of gestational hypertension and preeclampsia in twin pregnancies” [toxicology and applied pharmacology volume 503, October 2025, 117505] - Wei-Zhen Tang; Hong-Yu Xu; Qin-Yu Cai; Yun-Ren Pan; Hao-Wen Chen; Ya-Ting Jia; Tai-Hang Liu; Yong Heng Wang; Fei Han; Niya Zhou (Toxicology and Applied Pharmacology, 2025)

Preparation and characterization of PAPP@MF microcapsules for enhancing the safety of PVDF - Long-Tai Qi; Lei Ma; Zhi-Xiang Xing; Ye-Cheng Liu; Wan-Zheng Lu; Han Han; Tian-Yu Zhou; Yao Wu (Journal of Fluorine Chemistry, 2025)

Bifunctional coupled metal covalent organic framework MCOF-FeCu is used to implement bionic leaves - Keliang Wu; Bowen Peng; Qiaonan Yu; Qiang Liu; Bingke Li; Jinjun Tian; Zhiyong Liu; Yanlong Tai (Fuel, 2025)

Novel fused-bimacrocycles supply stepwise and orthogonal assembly, versatile way to construct multi-functional materials - Ting-Ting Huang; Xin-Yu Dai; Juan Liu; Tai-Bao Wei; Hong Yao; Bingbing Shi; Jin-Fa Chen; Qi Lin (Chemical Engineering Journal, 2025)

Efficient tanshinone metabolic engineering in Salvia miltiorrhiza through modified multiplex CRISPR/Cas9 system - Han Zheng; Qi Yao; Qi Liu; Badalahu Tai; Yi Ye; Ling Li; Yaojie Zhang; Yuyang Zhao; Xiaokai Gao; Shuai Liu; Xueqing Fu; Muyao Yu; et al. (Chemical Engineering Journal, 2025)

The different impacts of ambient air pollution exposure on the risks of gestational hypertension and preeclampsia in twin pregnancies - Wei-Zhen Tang; Hong-Yu Xu; Qin-Yu Cai; Yun-Ren Pan; Hao-Wen Chen; Ya-Ting Jia; Tai-Hang Liu; Yong Heng Wang; Fei Han; Niya Zhou (Toxicology and Applied Pharmacology, 2025)

Chemical composition and bioactivity of Uvaria micrantha from Vietnam - Fang-Rong Chang; Hao-Chun Hu; Szu-Yin Yu; Yi-Hong Tai; Hsin-Yi Tang (Phytochemistry Letters, 2025)

Revisiting the Indium Window effect: Insights from sphalerite big data - Qi-Nan Zou; Yu-Miao Meng; Rui-Zhong Hu; Xiao-Wen Huang; Xian-Wu Bi; Tai-Ping Zhao (Journal of Asian Earth Sciences, 2025)

Antifreeze peptides from Channa argus skin: Structural characterization and cryoprotective efficacy of peptide TA-14 - Wenhao Zhang; Yuexin Pan; Zhiyuan Tai; Wanzhou Yang; Xia Liu; Mingqian Wang; Xiaodong Yu; Qiyi He (Food Bioscience, 2025)

Halogen-sulfur synergy in benzodithiophene-benzodithienedione conjugated polymers: Molecular design of high-performance photoelectrodes for metal anti-corrosion - Rui Ding; Jin-ying Li; Yi-wen Zhang; Hao-han Cao; Xiao Liu; Yu-han Wang; Ming-di Lei; Yu-lin Zhang; An-lan Ji; Yu-chen Zhang; Jie Liu; Tai-jiang Gui; et al. (Chemical Engineering Journal, 2025)

Humidity-dependent ammonium formation and enhanced light scattering in agricultural aerosols - Chien-Hao Lin; Ling-Ya Chen; Ting-Yu Chiang; Sally C. W. Tai; Shih-Yu Chang (Environmental Geochemistry and Health, 2025)

Energy cycle efficiency of the EU - Tai-Yu Lin; Yung-ho Chiu; Pai-Yun Hsiao (Environment, Development and Sustainability, 2025)

Alisertib inhibits acute myeloid leukemia cell growth by inhibiting STAT3 activation - Pang-Ting Cheng; Ho Lin; Yu-Chiao Cheng; Tzu-Hung Hsiao; Pei-Pei Jhan; Jia-Rung Tsai; Mei-Chih Chen; Tai-Lin Chen; Chieh-Lin Jerry Teng (Toxicology and Applied Pharmacology, 2025)

Novel bispecific monoclonal antibody-based dual-analyte immunochromatographic strip for the detection of aflatoxin B1 and ochratoxin A in cereal samples - Shih-Wei Wu; Wei Hong Tai; Chia-Yu Hsieh; Biing-Hui Liu; Feng-Yih Yu (Food Chemistry, 2025)

Shear behavior of FRP-reinforced concrete beams with basalt FRP grids as shear reinforcements - JinJing Liao; Bo Di; Yu Zheng; Tai-Gu Chen; Jun-Jie Zeng; Yan Zhuge (Engineering Structures, 2025)

Beyond convention: Construction of β-cyclodextrin-based shape-changing particles capable of light-responsive control and bioactivity application - Pu-Ying Qi; Li-Hong Shi; Zhi-Cheng Zheng; Yu-Mei Feng; Tai-Hong Zhang; Rong-Shuang Luo; Shuai Tan; A-Ling Tang; Hou-Yun Huang; Xiang Zhou; Hong-Mei Xiang; Li-Wei Liu; et al. (Carbohydrate Polymers, 2025)

Assessing the impact of air pollution exposure on preterm birth risk in different subtypes of twin pregnancies and identifying critical sensitive windows - Xue-Bing Chen; Wei-Zhen Tang; Qin-Yu Cai; Tai-Hang Liu; Fei Han; Hong-Yu Xu; Yun-Ren Pan; Niya Zhou; Yong Heng Wang; Qiao Huang (Environmental Geochemistry and Health, 2025)

Enhanced therapeutic efficacy of Dioscorea cirrhosa Lour. n -butanol fractions in ulcerative colitis: a dual administration approach with comprehensive mucosal protection and anti-inflammatory effects - Mei Wang; XingJu Peng; CanJiao Yang; XinLong Yu; HaiChuan Tai; YanPing Li (Natural Product Research, 2025)

Methane dynamics controlled by subsurface metabolic architecture and tidal cycling in a mangrove wetland - Tzu-Hsuan Tu; Tai-Yi Lee; Zih-Huei Yu; Chun-Hung Lu; Yueh-Ting Lin; Pei-Ling Wang (Science of The Total Environment, 2025)

Construction of yeast two-hybrid cDNA library and identification of interacting protein with McHDRa/b in Matricaria chamomilla L. - Honggang Wang; Luyao Yu; Shuangshuang Li; Jin Wang; Wenjing Cheng; Siqing Zhu; Feng Shi; Yuling Tai; Yi Yuan (Plant Molecular Biology, 2025)

A preliminary study on the community structure of culturable planktonic and attached bacteria in the harbor of Qingdao, China - Shide Ma; Linlin Zhang; Yimeng Zhang; Yu Tai; Wen Han; Jinfeng Yang; Xin Shi; Bochao Lu; Jizhou Duan (Acta Oceanologica Sinica, 2025)

Predicting potential soil and groundwater contamination risks from gas stations using three machine learning models (XGBoost, LightGBM, and Random Forest) - Tai-Kuei Yu; I.-Cheng Chang; Shen-De Chen; Huey-Long Chen; Tai-Yi Yu (Process Safety and Environmental Protection, 2025)

Melatonin Promotes B-Cell Maturation and Attenuates Post-Ischemic Immunodeficiency in a Murine Model of Transient Focal Cerebral Ischemia - Shih-Huang Tai; Hao-Hsiang Hsu; Sheng-Yang Huang; Yu-Ning Chen; Liang-Yi Chen; Ai-Hua Lee; Ai-Chiang Lee; E.-Jian Lee (Journal of Neuroimmune Pharmacology, 2025)

Multigenerational ecotoxicity of tris(2-butoxyethyl) phosphate to the tropical water flea Ceriodaphnia cornuta and probabilistic ecological risk assessment in freshwater environments - Tan-Duc Nguyen; Van-Tai Nguyen; Khuong V. Dinh; Claudia Wiegand; Zhen Wang; Christine Baduel; Thanh Luu Pham; Thi Thuy Duong; Quoc-Hung Nguyen; Van Manh Do; Thi Phuong Quynh Le; Yu-Chen Huang; et al. (Aquatic Toxicology, 2025)

Isolation and Identification of Plant Growth-Promoting Endophytes Bacteria Highly Effective in Suppressing Damping-off in Sugar Beet - Bingchen Zou; Tai Li; Yonglong Liu; Zeyuan Cui; Lihua Yu; Gui Geng; Jiahui Liu; Yao Xu; Yuguang Wang (Sugar Tech, 2025)

Genetic structure and diversity of the red big eye Priacanthus macracanthus in the northwestern Pacific Ocean - Sheng-Tai Hsiao; Yu-Min Ju; Kui-Ching Hsu; Po-Hsun Kuo (Marine Biodiversity, 2025)
Understanding genetic diversity and population structure is essential for effective fisheries management. This study examined the population genetic structure, diversity, and demography of the red big eye Priacanthus macracanthus , a commercially crucial species in the western Pacific and eastern Indian Oceans, by using mitochondrial DNA cytochrome b ( cytb ) gene sequences (1,141 bp). A total of 206 samples were collected from 9 locations, and 101 haplotypes were obtained. Analysis revealed that (1) all haplotypes clustered into two sympatric haplogroups; (2) although the genetic distance between these haplogroups was small, nucleotide substitution patterns indicated distinct evolutionary histories; (3) migration and haplogroup distribution patterns suggested that the two haplogroups may have originated from different sources, eastern Indian Ocean and the western Pacific Ocean; and (4) recent population declines and low nucleotide diversity indicated a need for targeted management strategies. These findings provide valuable insights that can guide fisheries management and future research on the conservation of P. macracanthus populations.

Analysis of Wind–Wave Relationship in Taiwan Waters - Kai-Ho Cheng; Chih-Hsun Chang; Yi-Chung Yang; Yu-Hao Tseng; Chung-Ru Ho; Tai-Wen Hsu; Dong-Jiing Doong (Journal of Marine Science and Engineering, 2025)
The relationship between wind and waves has been extensively studied over time. However, understanding the local wind and wave relationship remains crucial for advancing renewable energy development and optimizing ocean management strategies. This study used wind and wave data collected by the ten weather buoys in the waters surrounding Taiwan to analyze regional sea states. The relationship between wind speed and significant wave height (SWH) was examined using regression analysis. Additionally, machine learning techniques were employed to assess the relative importance of features contributing to SWH growth. The regression analysis revealed that SWH in the waters surrounding Taiwan was not fully developed, with notable discrepancies observed between the waters east and west of Taiwan. According to the power law formula describing the relationship between wind speed and SWH, the eastern waters exhibited a larger prefactor coupled with a smaller scaling exponent, while the western waters manifested a converse parametric configuration. Through an evaluation of four machine learning algorithms, it was determined that wind speed is the most influential factor driving these regional differences, especially in the waters west of Taiwan. Beyond wind speed, air pressure or temperature emerged as the secondary feature factor governing wind–wave interactions in the waters east of Taiwan.

Vision transformer-based stratification of pre/diabetic and pre/hypertensive patients from retinal photographs for 3PM applications - Krithi Pushpanathan; Yang Bai; Xiaofeng Lei; Jocelyn Hui Lin Goh; Can Can Xue; Samantha Min Er Yew; Miaoli Chee; Ten Cheer Quek; Qingsheng Peng; Zhi Da Soh; Marco Chak Yan Yu; Jun Zhou; et al. (EPMA Journal, 2025)
Objective Diabetes and hypertension pose significant health risks, especially when poorly managed. Retinal evaluation though fundus photography can provide non-invasive assessment of these diseases, yet prior studies focused on disease presence, overlooking control statuses. This study evaluated vision transformer (ViT)-based models for assessing the presence and control statuses of diabetes and hypertension from retinal images. Methods ViT-based models with ResNet-50 for patch projection were trained on images from the UK Biobank ( n = 113,713) and Singapore Epidemiology of Eye Diseases study ( n = 17,783), and externally validated on the Singapore Prospective Study Programme ( n = 7,793) and the Beijing Eye Study ( n = 6064). Model performance was evaluated using the area under the receiver operating characteristic curve (AUROC) for multiple tasks: detecting disease, identifying poorly controlled and well-controlled cases, distinguishing between poorly and well-controlled cases, and detecting pre-diabetes or pre-hypertension. Results The models demonstrated strong performance in detecting disease presence, with AUROC values of 0.820 for diabetes and 0.781 for hypertension in internal testing. External validation showed AUROCs ranging from 0.635 to 0.755 for diabetes, and 0.727 to 0.832 for hypertension. For identifying poorly controlled cases, the performance remained high with AUROCs of 0.871 (internal) and 0.655–0.851 (external) for diabetes, and 0.853 (internal) and 0.792–0.915 (external) for hypertension. Detection of well-controlled cases also yielded promising results for diabetes (0.802 [internal]; 0.675–0.838 [external]), and hypertension (0.740 [internal] and 0.675–0.807 [external]). In distinguishing between poorly and well-controlled disease, AUROCs were more modest with 0.630 (internal) and 0.512–0.547 (external) for diabetes, and 0.651 (internal) and 0.639–0.683 (external) for hypertension. For pre-disease detection, the models achieved AUROCs of 0.746 (internal) and 0.523–0.590 (external) for pre-diabetes, and 0.669 (internal) and 0.645–0.679 (external) for pre-hypertension. Conclusion ViT-based models show promise in classifying the presence and control statuses of diabetes and hypertension from retinal images. These findings support the potential of retinal imaging as a tool in primary care for opportunistic detection of diabetes and hypertension, risk stratification, and individualised treatment planning. Further validation in diverse clinical settings is warranted to confirm practical utility.

Fluorescent nanozyme for the dual-mode detection of tetracycline: Aggregation-induced luminescence and boosting peroxidase-like activity - Tai Ye; Long Bai; Jinsong Yu; Weiyan Shi; Min Yuan; Juncheng Wang; Hui Cao; Liling Hao; Xiuxiu Wu; Fengqin Yin; Fei Xu (Food Control, 2025)

Evaluating European countries' progress towards SDGs: Insights from parallel SBM DEA analysis of economic, healthcare, environmental, and educational efficiencies - Tai-Yu Lin; Yung-Ho Chiu; Jia Sheng Lu; Liang-Chun Lu; Hsiu-Fang Chien (Journal of Environmental Management, 2025)

Geochemical constraints on the link between lunar magma ocean cumulates and the source of Chang'E-5 basalts from olivine trace element abundances - Yong Wu; Jie-Jun Jing; Zi-Ying Li; Ming-Kuan Qin; Ben-Xun Su; Jun Zhong; Dong-Fa Guo; Guang Fan; Rui-Ping Liu; Sheng He; Ting Li; Xiang-Kun Ge; et al. (Icarus, 2025)

Co-adsorption of methylene blue/Pb(II) from aqueous solutions using sulfonated mesoporous diatomite - Ali M. Abou-Elanwar; So Young Lee; Jeongkyun Yu; Jieun Kim; Chihyun Hwang; Hyungmin Park; Young-tai Noh; Ming Xie; Jiuyang Lin; Seong-Ju Park; Dong Han Seo; Youngjin Kim (Journal of Water Process Engineering, 2025)

Plasma proteomics identifies proteins and pathways associated with incident depression in 46,165 adults - Jujiao Kang; Liu Yang; Tianye Jia; Wei Zhang; Lin-Bo Wang; Yu-Jie Zhao; Jia You; Yue-Ting Deng; Yi-Jun Ge; Wei-Shi Liu; Yi Zhang; Yi-Lin Chen; et al. (Science Bulletin, 2025)

Specific nickel recovery using screen-printed carbon electrode electrografted with ionic liquid - Chun-Hao Tai; Shih-Hao Lin; Meng-Shun Huang; Hsiang-Yu Wang (Environmental Pollution, 2025)

Genomic analysis of modern maize inbred lines reveals diversity and selective breeding effects - Kaijian Fan; Mohsin Ali; Kunhui He; Yingwei Feng; Tingxi Yu; Hao Zhang; Tai An; Weiwei Zeng; Junjie Fu; Ying Zhou; Yanfang Heng; Fei Gu; et al. (Science China Life Sciences, 2025)

High diversity of strain clonality and metallo-β-lactamases genes among carbapenem-resistant Enterobacterales in Taiwan - Jia-Arng Lee; Yao-Wen Kuo; Shin-Hei Du; Tai-fen Lee; Chun-Hsing Liao; Yu-Tsung Huang; Po-Ren Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Overexpression of CYP6CY1 is Involved in Imidacloprid Resistance in Sitobion miscanthi (Takahashi) (Homoptera: Aphidae) - Yun-Shan Xiong; Ling-Ling Cui; Gui-Lei Hu; Yu-Tai Jiang; Yong-Po Lv; Pei Zhang; Jin-Song Zheng; Bai-Zhong Zhang; Run-Qiang Liu (Neotropical Entomology, 2025)

Functional analysis of (E)-β-farnesene synthases involved in accumulation of (E)-β-farnesene in German chamomile (Matricaria chamomilla L.) - Yuling Tai; Haiyan Wu; Lu Yang; Yi Yuan; Youhui Chen; Honggang Wang; Yifan Jin; Luyao Yu; Shuangshuang Li; Feng Shi (Plant Science, 2025)

Identification and molecular mechanism of a novel DPP-IV inhibitory tetrapeptide IPVK from rabbit meat proteins: Insights from in silico study and experimental validation - Haohan Hu; Jianfei Li; Xiya Chen; Haiting Zhu; Wenhao Zhang; Zhiyuan Tai; Xiaodong Yu; Qiyi He (Food Bioscience, 2025)

Changes in the small-molecule fingerprints of rice planted near an industrial explosion site in Taiwan - Wen-Ling Chen; Husan-Yu Tai; Chang-Chuan Chan; Hung-Chien Lin; Ting-Hsuan Hung; Mong-Hsun Tsai; Chia-Cheng Wei; Yu-San Han; Chuan-Chou Shen (Environmental Science and Pollution Research, 2024)

Unraveling the long-term gastrointestinal impact of perinatal perfluorobutane sulfonate exposure on rat offspring: Intestinal barrier dysfunction and Th17/Treg imbalance - Yongjie Liu; Yong Wang; Tai Ren; Guoqi Yu; Xi Meng; Liping Feng; Fei Li; Jun Zhang; Cuiping Wang (Science of The Total Environment, 2024)

Creating of novel Wx allelic variations significantly altering Wx expression and rice eating and cooking quality - Pei Zhao; Yuxia Liu; Zhuyun Deng; Lingtong Liu; Tengwei Yu; Gege Ge; Bingtang Chen; Tai Wang (Journal of Plant Physiology, 2024)

Vacuum-thermal alteration of lunar soil: Evidence from iron whiskers on troilite in Chang’e-5 samples - Chen Li; Yang Li; Kuixian Wei; Xiumin Chen; Kairui Tai; Zhuang Guo; Rui Li; Han Yu; Xiongyao Li; Wenhui Ma; Jianzhong Liu (Geochimica et Cosmochimica Acta, 2024)

A novel ACE inhibitory peptide from Douchi hydrolysate: Stability, inhibition mechanism, and antihypertensive potential in spontaneously hypertensive rats - Jianfei Li; Haohan Hu; Xiya Chen; Haiting Zhu; Wenhao Zhang; Zhiyuan Tai; Xiaodong Yu; Qiyi He (Food Chemistry, 2024)

D-ribose metabolic disorder and diabetes mellitus - Yu Tai; Zehong Zhang; Zhi Liu; Xiaojing Li; Zhongbin Yang; Zeying Wang; Liang An; Qiang Ma; Yan Su (Molecular Biology Reports, 2024)
D-ribose, an ubiquitous pentose compound found in all living cells, serves as a vital constituent of numerous essential biomolecules, including RNA, nucleotides, and riboflavin. It plays a crucial role in various fundamental life processes. Within the cellular milieu, exogenously supplied D-ribose can undergo phosphorylation to yield ribose-5-phosphate (R-5-P). This R-5-P compound serves a dual purpose: it not only contributes to adenosine triphosphate (ATP) production through the nonoxidative phase of the pentose phosphate pathway (PPP) but also participates in nucleotide synthesis. Consequently, D-ribose is employed both as a therapeutic agent for enhancing cardiac function in heart failure patients and as a remedy for post-exercise fatigue. Nevertheless, recent clinical studies have suggested a potential link between D-ribose metabolic disturbances and type 2 diabetes mellitus (T2DM) along with its associated complications. Additionally, certain in vitro experiments have indicated that exogenous D-ribose exposure could trigger apoptosis in specific cell lines. This article comprehensively reviews the current advancements in D-ribose’s digestion, absorption, transmembrane transport, intracellular metabolic pathways, impact on cellular behaviour, and elevated levels in diabetes mellitus. It also identifies areas requiring further investigation.

Insights from the international workshop on “Adapting agriculture to climate change and air pollution” - Evgenios Agathokleous; Lisa Emberson; Jie Pei; Kazuhiko Kobayashi; James D. Blande; Jo Cook; Chao Fang; Zhiyu Han; Hui Ju; Oliver Knopf; Tao Li; Bing Liu; et al. (Environmental Science and Pollution Research, 2024)

Chemical speciation and rice uptake of soil molybdenum-Investigation with X-ray absorption spectroscopy and isotope fractionation - Puu-Tai Yang; Yu-Hsuan Liang; Der-Chun Lee; Shan-Li Wang (Science of The Total Environment, 2024)

Unraveling the alternative process configurations for more environmentally friendly Maleic Anhydride production - Ting-Yu Yu; Ching-Tai Kuo; Cheng-Kai Lai; Wangyun Won; Bor-Yih Yu (Process Safety and Environmental Protection, 2024)

Sugar accumulation stage in sugar beets is a key stage in response to continuous cropping soil microbial community assembly - Tai Li; Rufei Cui; Gui Geng; Yinzhuang Dong; Yao Xu; Yanchun Sun; Piergiorgio Stevanato; Lihua Yu; Jiahui Liu; Vadim N. Nurminsky; Yuguang Wang (Plant and Soil, 2024)

Empowering green choices: how the new environmental paradigm influences consumer decisions for a sustainable circular economy - Tai-Yi Yu; Tai-Kuei Yu; Cheng-Min Chao (Environment, Development and Sustainability, 2024)

Identifying modifiable factors and their joint effect on frailty: a large population-based prospective cohort study - Ling-Zhi Ma; Yi-Jun Ge; Yi Zhang; Xi-Han Cui; Jian-Feng Feng; Wei Cheng; Lan Tan; Jin-Tai Yu (GeroScience, 2024)

Optimization of Cr(VI) ion-imprinted polymer with imidazole derivatives as functional monomers and its binding mechanism - Mengyuan Huang; Yuanyuan Yang; Hui Cao; Min Yuan; Tai Ye; Liling Hao; Jinsong Yu; Fengqin Yin; Fei Xu; Xiuxiu Wu (Journal of Environmental Chemical Engineering, 2024)

Ultrahigh-response flexible photothermoelectric photodetectors based on a graded Bi2Te3-carbon nanotube hybrid - Chao Chen; Hai-Long Yu; Yi-Ming Zhao; Peng-Xiang Hou; Shu-Yu Guo; Sheng-Qian Li; Hao-Zike Wang; Kaiping Tai; Chang Liu (Chemical Engineering Journal, 2024)

Arbuscular Mycorrhizal Fungi Enhance Tolerance to Drought Stress by Altering the Physiological and Biochemical Characteristics of Sugar Beet - Zeyuan Cui; Rui Chen; Tai Li; Bingchen Zou; Gui Geng; Yao Xu; Piergiorgio Stevanato; Lihua Yu; Vadim N. Nurminsky; Jiahui Liu; Yuguang Wang (Sugar Tech, 2024)

Active longevity and aging: dissecting the impacts of physical and sedentary behaviors on longevity and age acceleration - Ting Yu Lu; Jiao Wang; Chao Qiang Jiang; Ya Li Jin; Kar Keung Cheng; Tai Hing Lam; Wei Sen Zhang; Lin Xu (GeroScience, 2024)
Background To examine the associations of physical activity (PA) and sedentary behavior (SB) with longevity and age acceleration (AA) using observational and Mendelian randomization (MR) studies, and quantify the mediating effects of lipids. Methods In Guangzhou Biobank Cohort Study (GBCS), PA and SB were assessed by the Chinese Version of the International Physical Activity Questionnaire. Longevity was defined as participants whose age at follow-up or at death was at or above the 90th age percentile. AA was defined as the residual resulting from a linear model that regressed phenotypic age against chronological age. Linear regression and Poisson regression with robust error variance were used to assess the associations of total and specific PA in different intensities, and SB with AA and longevity, yielding βs or relative risks (RRs) and 95% confidence intervals (CIs). Two-sample MR was conducted to examine the causal effects. Mediation analysis was used to assess the mediating effects of lipids. Results Of 20,924 participants aged 50 + years in GBCS, during an average follow-up of 15.0 years, compared with low PA, moderate and high PA were associated with higher likelihood of longevity (RR (95% CI): 1.56 (1.16, 2.11), 1.66 (1.24, 2.21), respectively), and also cross-sectionally associated with lower AA (β (95% CI): -1.43 (-2.41, -0.45), -2.09 (-3.06, -1.11) years, respectively). Higher levels of moderate PA (MPA) were associated with higher likelihood of longevity and lower AA, whereas vigorous PA (VPA) showed opposite effects. The association of PA with longevity observed in GBCS was mediated by low-density lipoprotein cholesterol (LDL-C) by 8.23% (95% CI: 3.58–39.61%), while the association with AA was mediated through LDL-C, triglycerides and total cholesterol by 5.13% (3.94–7.30%), 7.81% (5.98–11.17%), and 3.37% (2.59–4.80%), respectively. Additionally, in two-sample MR, SB was positively associated with AA (β (95% CI): 1.02 (0.67, 1.36) years). Conclusions PA showed protective effects on longevity and AA, with the effects being partly mediated through lipids. Conversely, SB had a detrimental impact on AA. MPA was associated with higher likelihood of longevity and reduced AA, whereas VPA showed adverse effects. Our findings reinforce the recommendation of “sit less and move more” to promote healthy longevity, and highlight the potential risks associated with VPA in the elderly.

Solution-processable organic–inorganic materials with colorful afterglow at room temperature - Sheng-Hua Li; Tuo-Yu Zhou; Shu-Yue Yang; Tai-Wen Li; Penglin Zhang; Guang-Yue Li; Chang Li; Hong-Qiao Li; Jing-Yi Li; Qian Zhao (Chemical Engineering Journal, 2024)

Advanced combustion in heavy fuel aircraft piston engines: A comprehensive review and future directions - Longtao Shao; Yu Zhou; Tai Geng; Shuai Zhao; Kun Zhu; Zhiming Zhong; Huansong Yan; Tao Yu; Zheng Xu; Shuiting Ding (Fuel, 2024)

Dynamics of soil properties and microbial communities by crop rotation length: unveiling the key factors for enhanced sugar yield - Bingchen Li; Gui Geng; Tai Li; Shoujie Song; Yao Xu; Lihua Yu; Yuguang Wang (Plant and Soil, 2024)

Formation and growth of nanophase iron particles on the surface of Mercury revealed by experimental study - Ronghua Pang; Yang Li; Chen Li; Pengfei Zhang; Zhuang Guo; Sizhe Zhao; Han Yu; Li Wang; Chenxi Zhu; Shuangyu Wang; Kairui Tai; Qinwei Zhang; et al. (Acta Geochimica, 2024)

Intense NIR mechanoluminescence from Al3+-regulated MgGa2O4: Cr3+ - Xin Yu; Xin-Xin Yang; Jun Huan; Jia Tong; Yuhui Qiao; Juan-Juan Xing; Zhi-Jun Zhang; Jing-Tai Zhao (Chemical Engineering Journal, 2024)

Erratum to: Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2024)

Evolution and control of overburden fracture in extra-thick coal seam mining with hard roofs: ground grouting sealing and case study - Xianglin Dai; Rui Gao; Feng Du; Bin Yu; Xiangbin Meng; Yang Tai (Bulletin of Engineering Geology and the Environment, 2024)

Influence of gestational hypertension and maternal air pollutant exposure on birth outcomes - Tai-Ho Hung; Te-Yao Hsu; Jie Hsu; Chia-Yu Ou; Pi-Hua Liu; Liang-Ming Lo; Steven W Shaw; Gwo-Hwa Wan (Environmental Science and Pollution Research, 2024)

Whole exome sequencing analyses reveal novel genes in telomere length and their biomedical implications - Wei-Shi Liu; Bang-Sheng Wu; Liu Yang; Shi-Dong Chen; Ya-Ru Zhang; Yue-Ting Deng; Xin-Rui Wu; Xiao-Yu He; Jing Yang; Jian-Feng Feng; Wei Cheng; Yu-Ming Xu; et al. (GeroScience, 2024)

Climate-regulation of organic carbon export in erosive mountain settings: A case study from Taiwan since the last glacial maximum - Li-Wei Zheng; Robert G. Hilton; Yuan-Pin Chang; Rick J. Yang; Xiaodong Ding; Xufeng Zheng; Tsung-Yu Lee; Hsi-Jih Lu; Jung-Tai Lu; Yu-Shih Lin; James T. Liu; Shuh-Ji Kao (Quaternary Science Reviews, 2024)

microRNA-3037 targeting CYP6CY2 confers imidacloprid resistance to Sitobion miscanthi (Takahashi) - Bai-Zhong Zhang; Yu-Tai Jiang; Ling-Ling Cui; Gui-Lei Hu; Xin-An Li; Pei Zhang; Xiang Ji; Ping-Chuan Ma; Fan-Bin Kong; Run-Qiang Liu (Pesticide Biochemistry and Physiology, 2024)

A stable delivery system for curcumin: Fabrication and characterization of self-assembling acylated kidney bean protein isolate nanogels - Zhihui Yu; Yating Gao; Ziqi Shang; Tengfei Wang; Xuli He; Jian Lei; Fei Tai; Lixin Zhang; Yisheng Chen (Food Chemistry, 2024)

Modulations of ocean-atmosphere interactions on squid abundance over Southwest Atlantic - Chia-Ying Ko; Yu-Chi Lee; Yi-Chi Wang; Huang-Hsiung Hsu; Chun Hoe Chow; Ruei-Gu Chen; Tsung-Han Liu; Chih-Shin Chen; Tai-Sheng Chiu; Don-Hsieh Chiang; Ren-Fen Wu; Wan-Ling Tseng (Environmental Research, 2024)

Laboratory study on the frost-proof performance of a molecular vibration infrared Nano-thermoprobe (MVINT) embankment in seasonally frozen ground regions - Zhijian Wu; Guoxu Wang; Jun Bi; Wang Cao; Chengxin Chu; Yu Lu; Tian Sun; Bowen Tai (Cold Regions Science and Technology, 2024)

Identifying modifiable factors and their joint effect on brain health: an exposome-wide association study - Liang-Yu Huang; Yi-Jun Ge; Yan Fu; Yong-Li Zhao; Ya-Nan Ou; Yi Zhang; Ling-Zhi Ma; Shi-Dong Chen; Ze-Xin Guo; Jian-Feng Feng; Wei Cheng; Lan Tan; et al. (GeroScience, 2024)

Marinobacter albus sp. nov., Isolated from Sand Sediment in a Coastal Intertidal Zone - Tai-Hang Deng; Yu Zhang; Wen-Wu Zhang; Yue Su; Jia-Wei Gao; Jun-Jie Ying; Lin Xu; Xiao-Ming Xia; Cong Sun (Current Microbiology, 2024)

Nanoengineered M1 macrophages enhance photodynamic therapy of melanoma through oxygen production and subsequent antitumor immunity - Xinyue Zhang; Leilei Bao; Zhiliang Yu; Fengze Miao; Lisha Li; Zhen Cui; Huijun Pan; Zhiyu Qian; Tingrui Zhang; Yujing Zhao; Zongguang Tai; Quangang Zhu; et al. (Chemical Engineering Journal, 2024)

Extinction coefficient of dry and deliquescent chemical components of PM_(2.) 5 in urban areas and their impacts on visibility deterioration - Chien-Hao Lin; Shao-En Sun; Chung-Te Lee; Ting-Yu Chiang; Shih-Yu Chang; Tzu-Shuan Wu; Hsin-Yu Wei; Ling-Ya Chen; Hao-Wei Liu; Sally C.W. Tai (Atmospheric Pollution Research, 2024)

Identification of superior and rare haplotypes to optimize branch number in soybean - Hui Yu; Javaid Akhter Bhat; Candong Li; Beifang Zhao; Moran Bu; Zhirui Zhang; Tai Guo; Xianzhong Feng (Theoretical and Applied Genetics, 2024)
Key message Using the integrated approach in the present study, we identified eleven significant SNPs, seven stable QTLs and 20 candidate genes associated with branch number in soybean . Abstract Branch number is a key yield-related quantitative trait that directly affects the number of pods and seeds per soybean plant. In this study, an integrated approach with a genome-wide association study (GWAS) and haplotype and candidate gene analyses was used to determine the detailed genetic basis of branch number across a diverse set of soybean accessions. The GWAS revealed a total of eleven SNPs significantly associated with branch number across three environments using the five GWAS models. Based on the consistency of the SNP detection in multiple GWAS models and environments, seven genomic regions within the physical distance of ± 202.4 kb were delineated as stable QTLs. Of these QTLs, six QTLs were novel, viz., qBN7 , qBN13, qBN16, qBN18, qBN19 and qBN20 , whereas the remaining one, viz., qBN12 , has been previously reported. Moreover, 11 haplotype blocks, viz., Hap4, Hap7, Hap12, Hap13A, Hap13B, Hap16, Hap17, Hap18, Hap19A, Hap19B and Hap20, were identified on nine different chromosomes. Haplotype allele number across the identified haplotype blocks varies from two to five, and different branch number phenotype is regulated by these alleles ranging from the lowest to highest through intermediate branching. Furthermore, 20 genes were identified underlying the genomic region of ± 202.4 kb of the identified SNPs as putative candidates; and six of them showed significant differential expression patterns among the soybean cultivars possessing contrasting branch number, which might be the potential candidates regulating branch number in soybean. The findings of this study can assist the soybean breeding programs for developing cultivars with desirable branch numbers.

Lack of effects of eight-week left dorsolateral prefrontal theta burst stimulation on white matter macro/microstructure and connection in autism - Chun-Hung Yeh; Po-Chun Lin; Rung-Yu Tseng; Yi-Ping Chao; Chen-Te Wu; Tai-Li Chou; Rou-Shayn Chen; Susan Shur-Fen Gau; Hsing-Chang Ni; Hsiang-Yuan Lin (Brain Imaging and Behavior, 2024)

Circulating exosome-mediated AMPKα–SIRT1 pathway regulates lipid metabolism disorders in calf hepatocytes - Daoliang Zhang; Hongyan Ding; Chang Liu; Yingying Huang; Wenjun Tai; Shibin Feng; Xichun Wang; Chang Zhao; Yu Li (Research in Veterinary Science, 2024)

Inflammation and Brain Structure in Alzheimer’s Disease and Other Neurodegenerative Disorders: a Mendelian Randomization Study - Wei-Shi Liu; Ya-Ru Zhang; Yi-Jun Ge; Hui-Fu Wang; Wei Cheng; Jin-Tai Yu (Molecular Neurobiology, 2024)

MiR-26b-3p Promotes Intestinal Motility Disorder by Targeting FZD10 to Inhibit GSK3β/β-Catenin Signaling and Induce Enteric Glial Cell Apoptosis - Yu Zhan; Yong Wen; Fan Zheng; Li-juan Du; Tai-yu Chen; Xu-long Shen; Rong Wu; Xue-gui Tang (Molecular Neurobiology, 2024)

Air pressure law of a reservoir constructed in karst sinkholes - Bo Yu; Shengping Tai; Kexun Zheng; Shiwan Chen; Xiao Han; Senlin Wang; Shuangying Zuo (Journal of Mountain Science, 2024)

Feasibility assessment of replacing fishmeal with Clostridium autoethanogenum protein in commercial whiteleg shrimp diets: Impacts on growth, muscle characteristics, and health - Yi-Chun Kuo; Thi Hang Ho; Anant Bharadwaj; Hoang Trieu Quan Tran; Yu-Ting Chu; Su-Hua Wang; Tai-Yuan Chen; Fan-Hua Nan; Po-Tsang Lee (Animal Feed Science and Technology, 2024)

Assessment of sources and health risks of heavy metals in metropolitan household dust among preschool children: The LEAPP-HIT study - Chi-Sian Kao; Ying-Lin Wang; Chuen-Bin Jiang; Pei-Ju Tai; Yi-Hua Chen; Hsing-Jasmine Chao; Yu-Chun Lo; Zeng-Yei Hseu; Hsing-Cheng Hsi; Ling-Chu Chien (Journal of Environmental Management, 2024)

Rigorous simulation and comprehensive analysis for the novel glycerol carbonate (GC) production process via indirect conversion of CO2 - Pei-Jhen Wu; Chun-Cheng Hsu; Bor-Yih Yu; Shiang-Tai Lin (Fuel, 2024)

Effect of excitation frequency and joint density on the dynamic amplification effect of slope surface on jointed rock slopes - Daping Tai; Shengwen Qi; Bowen Zheng; Guangming Luo; Jianxian He; Songfeng Guo; Yu Zou; Zan Wang (Engineering Geology, 2024)

Linkage analysis for water-energy-economic system efficiency in China - Zhong Fang; Yung-ho Chiu; Yiqin Chen; Tai-Yu Lin; Tzu-Han Chang (Environment, Development and Sustainability, 2024)

Astronomically forced late Paleocene-early Eocene climate variability in the Subei Basin, East China - Juan Liu; Xiaodong Ma; Yongchao Lu; James G. Ogg; Wenrui Yu; Zhiqi Qian; Ze Zhang; Hao Tai; Zhanhong Liu; David B. Kemp; Chunju Huang (Global and Planetary Change, 2024)

Hard Roof’s 3D Breaking Characteristics for Longwall Faces Mined via Roof-Cutting Technology with a Chainsaw Arm Machine - Yang Tai; Tiejun Kuang; Bin Yu; Yong Li; Wenyang Zhang; Xiangbing Meng (Rock Mechanics and Rock Engineering, 2024)

Application of high-dimensional uniform manifold approximation and projection (UMAP) to cluster existing landfills on the basis of geographical and environmental features - Teng-To Yu; Chun-Yuan Chen; Tai-Hsi Wu; Yu-Chen Chang (Science of The Total Environment, 2023)

Discovery and verification of bitter components in Panax notoginseng based on the integrated strategy of pharmacophore model, system separation and bitter tracing technology - Jing Yang; Min Qiu; Tai Lu; Shangdong Yang; Ji Yu; Junzhi Lin; Hongyan Ma; Zhiping Guo; Zhencai Chen; Xue Han; Dingkun Zhang (Food Chemistry, 2023)

Agricultural production efficiency, food consumption, and food waste in the European countries - Tai-Yu Lin; Shih-Yung Chiu; Yung-ho Chiu; Liang-Chun Lu; Kuei-Ying Huang (Environment, Development and Sustainability, 2023)

Socioeconomic status, lifestyle and risk of incident dementia: a prospective cohort study of 276730 participants - Ya-Nan Ou; Yan-Bo Zhang; Yu-Zhu Li; Shu-Yi Huang; Wei Zhang; Yue-Ting Deng; Bang-Sheng Wu; Lan Tan; Qiang Dong; An Pan; Ren-Jie Chen; Jian-Feng Feng; et al. (GeroScience, 2023)

Aquaculture net cleaning with cavitation improves biofouling removal - Tai-Ping Yuan; Xiao-Hua Huang; Yu Hu; Shao-Min Wang; Qi-You Tao; Guo-Liang Pang (Ocean Engineering, 2023)

A novel pulse-decay-balance method for smooth rock joint aperture measurement - Xuan-Xinh Nguyen; Pin-Lun Tai; Jia-Jyun Dong; Chi-Wen Yu (International Journal of Rock Mechanics and Mining Sciences, 2023)

Profit-seeking enterprise production and business waste treatment efficiency in Taiwan - Tai-Yu Lin; Yung-Ho Chiu; Yi-Nuo Lin; Tzu-Han Chang (Environment, Development and Sustainability, 2023)

Neurobiological effects of exercise intervention for premenstrual syndrome - Ren-Jen Hwang; Hsin-Ju Chen; Lee-Fen Ni; Tai-Ying Liu; Yu-Ling Shih; Yueh-O. Chuang (Cognitive Neurodynamics, 2023)

High-performance peptide and disulfide mapping by direct injection of intact proteins using on-line coupled UV-liquid chromatography microdroplet mass spectrometry (UVLC-MMS) - Chin-Ming Kuo; Hung-Hsiang Jen; Fung-Yu Chen; Mohsen Akbarian; Tai-Hong Ou; Kang-Yu Liu; Jung-Lee Lin; Shu-Hui Chen (Analytica Chimica Acta, 2023)

Investigating the Ice-Induced Fatigue Damage of Offshore Structures by Field Observations - Yating Huang; Songsong Yu; Tai An; Guojun Wang; Dayong Zhang (Journal of Marine Science and Engineering, 2023)
The oil and natural gas resources of the Bohai Sea are mainly marginal oil fields, and there are currently a large number of structures that are approaching or have reached the end of their service life called aging structures. The interactions between ice and offshore structures could lead to significant ice-induced vibration. Ice-induced vibrations may evoke fatigue damage in tubular joints, which results in severe dangers for offshore platforms in the Bohai Sea. Dynamic ice force models and sea ice fatigue environmental parameters have not been well developed in the current design codes. It is not accurate to evaluate the fatigue damage of structures only with numerical simulation. In this paper, a faster method for evaluating fatigue damage on aging structures is proposed. Firstly, the approximate linear relationship between the fatigue hot spot stress and the vibration response of the deck structure has been discovered using dynamic analysis for jacket platform of Bohai Sea. Then, the procedure of the fatigue damage evaluation of the aging structures in the Bohai Sea is established. Finally, the numerical simulation of the structure is carried out considering ice thickness, ice velocity, ice direction, and action height of sea ice. Fatigue damage is calculated by the fatigue hot spot stress and the Palmgren–Miner rule. The measured data on the platform in the Bohai Sea are selected to obtain the fatigue hot spot stress using a mathematical model. The fatigue damage results considering the actual ice conditions of a jacket structure in the Bohai Sea are compared using the proposed method and finite element analysis. The comparison of the results verifies the rationality of the method proposed in this work.

Optimal maintenance planning for offshore wind farms under an uncertain environment - Tai-Sheng Su; Xin-Yu Weng; Vincent F. Yu; Chin-Chun Wu (Ocean Engineering, 2023)

Dynamic total factors’ environmental efficiency in European union countries - Ching-Cheng Lu; Yung-ho Chiu; I-Fang Lin; Tai-Yu Lin (Environment, Development and Sustainability, 2023)

The association of bisphenol A and paraben exposure with sensorineural hearing loss in children - Chia-Huang Chang; Chun-Ting Lu; Tai-Ling Chen; Wen-Tzu Huang; Pao-Chuan Torng; Chen-Wei Chang; Yu-Chun Chen; Yu-Lin Yu; Yung-Ning Chuang (Environmental Science and Pollution Research, 2023)

Incentives for promoting climate change adaptation technologies in agriculture: an evolutionary game approach - Yong Sun; Ruihui Yu; Tai Chiu Edwin Cheng (Environmental Science and Pollution Research, 2023)

Terrestrial sources regulate the endogenous phosphorus load in Taihu Lake, China after exogenous controls: Evidence from a representative lake watershed - Hezhong Yuan; Panyu Chen; Enfeng Liu; Jianghua Yu; Ziqiu Tai; Qiang Li; Haixiang Wang; Yiwei Cai (Journal of Environmental Management, 2023)

Migration of hazardous substances during peanut oil squeezing for their dietary assessment - Bolei Yang; Xiaohua Yu; Jihao Shan; Xiaoyu Tian; Tosin Victor Adegoke; Shuo Yang; Gang Wang; Bowen Tai; Junning Ma; Qiang Yu; Fuguo Xing (Food Control, 2023)

Defective Ru-doped α-MnO2 nanorods enabling efficient hydrazine oxidation for energy-saving hydrogen production via proton exchange membranes at near-neutral pH - Zhipeng Yu; Chaowei Si; Ferran Sabaté; Alec P. LaGrow; Zhixin Tai; Vlad Martin Diaconescu; Laura Simonelli; Lijian Meng; Maria J. Sabater; Bo Li; Lifeng Liu (Chemical Engineering Journal, 2023)

Spawning characteristics of blue sprat (Spratelloides gracilis) in the waters of Penghu, central Taiwan Strait - Li Chi Cheng; Yang Chi Lan; Kuo Wei Lan; Jinn Shing Weng; Yu Kai Chen; Sheng Tai Hsiao; Yi Sui Wu; Jia Shin He; Hsing Han Huang; Yu Cih Huang; Hung An Cheng (Frontiers in Marine Science, 2023)
Blue sprat ( Spratelloides gracilis ) is an economically valuable species that inhabits the central Taiwan Strait. However, despite the implementation of a local management scheme involving a closed season between 1 May and 1 June, the annual catch has rapidly decreased over the decades. Thus, the efficacy of the implemented regulations must be investigated. This study sought to clarify the reproductive biology, spawning ground, and behavior of this species in the waters of Penghu. In total, 6,549 specimens were collected between March 2021 and September 2022. Considering gonadosomatic index, group maturity, and oocyte diameter, we found that the spawning season (March–September) peaked in April; new cohorts were distinctly recruited after the spawning peak. The distribution of the spawning ground (latitude, 23°41′N to 23°43′N; longitude, 119°32′E to 119°39′E) was determined by considering the fishing area of mature females and DNA analysis of adhered eggs. We further noted shoals of fish darting in the bottom water without clear schooling movement, females’ abdomen frequently contacting substrata for eggs able to attach on during oviposition, and males releasing sperms making water milky white; these indicate that S. gracilis exhibits promiscuous spawning behavior. Our findings may facilitate the management and conservation of S. gracilis in this region.

Four cases of reported adverse effects from black boletoi, Anthracoporus nigropurpureus (Boletaceae) mushroom ingestion - Jing Ma; Jing Xia; Hai-Jiao Li; Lin-Jie Su; Rou Xue; Shuai Jiang; Tai-Jie Yu; Yi Liu; Li-Ping Tang (Toxicon, 2023)

Interaction of upwelling asthenosphere with oceanic lithospheric mantle in Bangong-Nujiang subduction zone: A new mechanism for the petrogenesis of Nb-enriched basalts - Qiang-Tai Huang; Cheng-Lei Zhang; Kai-Jun Zhang; Yuan-Jun Hua; Wen-Chao Chen; Yu-Dong Cao; Peng Cheng (Lithos, 2023)

Phosphorus doping significantly enhanced the catalytic performance of cobalt-single-atom catalyst for peroxymonosulfate activation and contaminants degradation - Ning Chen; Yu Zeng; Tai Li; Peixin Cui; Dionysios D. Dionysiou; Xiaolei Wang; Cun Liu; Guodong Fang; Chengcheng Ding; Yuan Zhao; Juan Gao; Yujun Wang; et al. (Journal of Hazardous Materials, 2023)

Ganglioside-focused Glycan Array Reveals Abnormal Anti-GD1b Auto-antibody in Plasma of Preclinical Huntington’s Disease - Tien-Wei Lin; Jung-Kai Chang; Yih-Ru Wu; Tsung-Hsien Sun; Yang-Yu Cheng; Chien-Tai Ren; Mei-Hung Pan; Jin-Lin Wu; Kuo-Hsuan Chang; Hwai-I Yang; Chiung-Mei Chen; Chung-Yi Wu; et al. (Molecular Neurobiology, 2023)

Application of the metal ions as potential population biomarkers for wastewater-based epidemiology: estimating tobacco consumption in Southern China - Lei Xu; Yu-ting Lu; Dong-feng Wu; Xuan Li; Min Song; Tai-jun Hang; Meng-xiang Su (Environmental Geochemistry and Health, 2023)

Root biomechanical features and wind erosion resistance of three native leguminous psammophytes for coastal dune restoration - Jung-Tai Lee; Cheng-Ying Shih; Yu-Shan Hsu (Ecological Engineering, 2023)

Cadmium exposure induces histological damage and cytotoxicity in the cardiovascular system of mice - Shing-Hsien Chou; Hung-Chen Lin; Shao-Wei Chen; Yu-Ting Tai; Shih-Ming Jung; Fu-Hsiang Ko; Jong-Hwei Su Pang; Pao-Hsien Chu (Food and Chemical Toxicology, 2023)

A promising non-fullerene acceptor for near-infrared organic photodetectors operating with low dark current and high response speed - Yu-Ching Huang; Zhi-Hao Huang; Tai-Yung Wang; Priyanka Chaudhary; Jen-Fu Hsu; Kun-Mu Lee (Chemical Engineering Journal, 2023)

Urinary di-(2-ethylhexyl) phthalate metabolites are independently related to serum neurofilament light chain, a biomarker of neurological diseases, in adults: results from NHANES 2013–2014 - An-Ming Yang; Tai-Shuan Lai; Yu-Ling Lin; ChiKang Wang; Chien-Yu Lin (Environmental Science and Pollution Research, 2023)

Circulating polyunsaturated fatty acids, fish oil supplementation, and risk of incident dementia: a prospective cohort study of 440,750 participants - Yu He; Shu-Yi Huang; Hui-Fu Wang; Wei Zhang; Yue-Ting Deng; Ya-Ru Zhang; Qiang Dong; Jian-Feng Feng; Wei Cheng; Jin-Tai Yu (GeroScience, 2023)

Analysis of natural disasters and energy efficiency in China - Zhong Fang; Yung-ho Chiu; Tai-Yu Lin; Tzu-Han Chang; Yi-Nuo Lin (Environment, Development and Sustainability, 2023)

Transcription factor CncC potentially regulates cytochrome P450 CYP321A1-mediated flavone tolerance in Helicoverpa armigera - Chunni Zhang; Xinxiang Wang; Shulei Tai; Lijun Qi; Xiaoting Yu; Wu Dai (Pesticide Biochemistry and Physiology, 2023)

Multiple low-dose radiation-induced neuronal cysteine transporter expression and oxidative stress are rescued by N-acetylcysteine in neuronal SH-SY5Y cells - Ji-Young Yoo; Ye-Ji Lee; Yu-Jin Kim; Tai-Kyoung Baik; Jun-Ho Lee; Mi‑Jo Lee; Ran-Sook Woo (NeuroToxicology, 2023)

Mantle structure and dynamics at the eastern boundary of the northern Cascadia backarc - Claire A. Currie; Deirdre A. Mallyon; Tai-Chieh Yu; Yunfeng Chen; Andrew J. Schaeffer; Pascal Audet; Yu Jeffrey Gu (Journal of Geodynamics, 2023)

Machine learning approaches to predict the apparent rate constants for aqueous organic compounds by ferrate - Shan-Shan Zheng; Wan-Qian Guo; Hao Lu; Qi-Shi Si; Bang-Hai Liu; Hua-Zhe Wang; Qi Zhao; Wen-Rui Jia; Tai-Ping Yu (Journal of Environmental Management, 2023)

Risk assessment of methylmercury and species identification in shark meats ingested by Taiwan children - Bi-Yu Liu; I-Win Chen; Po-Wei Chen; Tai-Yuan Chen; Deng-Fwu Hwang (Food Control, 2023)

SecReT6 update: a comprehensive resource of bacterial Type VI Secretion Systems - Jianfeng Zhang; Jiahao Guan; Meng Wang; Gang Li; Marko Djordjevic; Cui Tai; Hui Wang; Zixin Deng; Zhaoyan Chen; Hong-Yu Ou (Science China Life Sciences, 2023)

Classifying Temporomandibular Disorder with Artificial Intelligent Architecture Using Magnetic Resonance Imaging - Zih-Kai Kao; Neng-Tai Chiu; Hung-Ta Hondar Wu; Wan-Chen Chang; Ding-Han Wang; Yen-Ying Kung; Pei-Chi Tu; Wen-Liang Lo; Yu-Te Wu (Annals of Biomedical Engineering, 2023)

Root cell wall remodeling: A way for exopolysaccharides to mitigate cadmium toxicity in rice seedling - Hong-yu Wei; Yi Li; Jiao Yan; Shuai-ying Peng; Sai-jin Wei; Yanbin Yin; Kun-tai Li; Xin Cheng (Journal of Hazardous Materials, 2023)

Greenhouse gas emission indicators, energy consumption efficiency, and optimal carbon emission allowance allocation of the EU countries in 2030 - Tai-Yu Lin; Yung-Ho Chiu; Yi-Nuo Lin; Tzu-Han Chang; Pei-Yu Lin (Gas Science and Engineering, 2023)

Analysis of the most efficient horizontal drainage position in the large strain consolidation considering the self-weight effect - Chun-Tai Xu; Zhong-Jin Wang; Xin-Yu Xie; Ling-Wei Zheng (Computers and Geotechnics, 2023)

Facile synthesis of spiro-core-based hole-transporting material for high-performance and stable perovskite solar cells - Kun-Mu Lee; Seid Yimer Abate; June Hung Yang; Wei-Hao Chiu; Seoungjun Ahn; Sie-Rong Li; Kang-Ling Liau; Yu-Tai Tao; Yan-Duo Lin (Chemical Engineering Journal, 2023)

Comparative Study of Two Common In Vitro Models for the Pancreatic Islet with MIN6 - Xinxin Chao; Furong Zhao; Jiawei Hu; Yanrong Yu; Renjian Xie; Jianing Zhong; Miao Huang; Tai Zeng; Hui Yang; Dan Luo; Weijie Peng (Tissue Engineering and Regenerative Medicine, 2023)

Cholesterol homeostasis regulated by ABCA1 is critical for retinal ganglion cell survival - Jialiang Yang; Yuhong Chen; Tongdan Zou; Bai Xue; Fang Yang; Xiangzhou Wang; Yibo Huo; Boyun Yan; Yuxia Xu; Shiyu He; Yi Yin; Jing Wang; et al. (Science China Life Sciences, 2023)

Bioactive icetexane and abietane diterpenes from Isodon phyllopodus - Rui Deng; Juan Zou; Chen-Liang Zhao; Ye-Meng Yang; Chuen Fai Ku; Yu Zhu; Zheng-Ming Liang; Jiang-Hai Ye; Lu-Tai Pan; Hong-Jie Zhang (Natural Product Research, 2023)

Numerical investigations of Lamb waves excited by interdigital transducers and incident on piezoelectric plates - Tai-Ho Yu (Wave Motion, 2023)

Two-stage dynamic data envelopment analysis measuring the overall efficiency and productivity changes of industry and agriculture in EU countries - Ching-Cheng Lu; I-Fang Lin; Tai-Yu Lin; Yung-ho Chiu (Journal of Cleaner Production, 2023)

Consistent control strategy for CO2 refrigeration systems based on refrigerant charge management - Yu-Jia He; Ying-Di Tai; Xiao-Xuan Zhao; Chun-Lu Zhang (International Journal of Refrigeration, 2023)

Residential greenness and risk of incident dementia: A prospective study of 375,342 participants - He-Ying Hu; Ya-Hui Ma; Yue-Ting Deng; Ya-Nan Ou; Wei Cheng; Jian-Feng Feng; Lan Tan; Jin-Tai Yu (Environmental Research, 2023)

Intramolecular D-A structure and n-π* transition co-promoted photodegradation activity of carbon nitride: Performance, mechanism and toxicity insight - Jingmin Shi; Meng Tai; Jingyang Hou; Yu Qiao; Chunbo Liu; Tianyu Zhou; Liang Wang; Bo Hu (Chemical Engineering Journal, 2023)

13.2% EQE near-infrared TADF OLED with emission peak at 761 nm - Jing-Wen Tai; Yukun Tang; Kai Zhang; Chen-Zong Yang; Ze-Hui Pan; Yu-Ching Lin; Yu-Wei Shih; Chia-Hsun Chen; Tien-Lung Chiu; Jiun-Haw Lee; Chuan-Kui Wang; Chung-Chih Wu; et al. (Chemical Engineering Journal, 2023)

Exopolysaccharides from Lactobacillus plantarum reduces cadmium uptake and mitigates cadmium toxicity in rice seedlings - Kun-tai Li; Shuai-ying Peng; Bao Zhang; Wei-fu Peng; Shui-jing Yu; Xin Cheng (World Journal of Microbiology and Biotechnology, 2022)

Mesenchymal Stem Cell Secreted-Extracellular Vesicles are Involved in Chondrocyte Production and Reduce Adipogenesis during Stem Cell Differentiation - Yu-Chen Tsai; Tai-Shan Cheng; Hsiu-Jung Liao; Ming-Hsi Chuang; Hui-Ting Chen; Chun-Hung Chen; Kai-Ling Zhang; Chih-Hung Chang; Po-Cheng Lin; Chi-Ying F. Huang (Tissue Engineering and Regenerative Medicine, 2022)
Background: Extracellular vesicles (EVs) are derived from internal cellular compartments, and have potential as a diagnostic and therapeutic tool in degenerative disease associated with aging. Mesenchymal stem cells (MSCs) have become a promising tool for functional EVs production. This study investigated the efficacy of EVs and its effect on differentiation capacity. Methods: The characteristics of MSCs were evaluated by flow cytometry and stem cell differentiation analysis, and a production mode of functional EVs was scaled from MSCs. The concentration and size of EVs were quantitated by Nanoparticle Tracking Analysis (NTA). Western blot analysis was used to assess the protein expression of exosome-specific markers. The effects of MSC-derived EVs were assessed by chondrogenic and adipogenic differentiation analyses and histological observation. Results: The range of the particle size of adipose-derived stem cells (ADSCs)- and Wharton’s jelly -MSCs-derived EVs were from 130 to 150 nm as measured by NTA, which showed positive expression of exosomal markers. The chondrogenic induction ability was weakened in the absence of EVs in vitro . Interestingly, after EV administration, type II collagen, a major component in the cartilage extracellular matrix, was upregulated compared to the EV-free condition. Moreover, EVs decreased the lipid accumulation rate during adipogenic induction. Conclusion: The results indicated that the production model could facilitate production of effective EVs and further demonstrated the role of MSC-derived EVs in cell differentiation. MSC-derived EVs could be successfully used in cell-free therapy to guide chondrogenic differentiation of ADSC for future clinical applications in cartilage regeneration.

Shanghai Autism Early Development: An Integrative Chinese ASD Cohort - Yuan Dai; Yuqi Liu; Lingli Zhang; Tai Ren; Hui Wang; Juehua Yu; Xin Liu; Zilin Chen; Lin Deng; Minyi Tao; Hangyu Tan; Chu-Chung Huang; et al. (Neuroscience Bulletin, 2022)

The outbreak of COVID-19 in Taiwan in late spring 2021: combinations of specific weather conditions and related factors - Shih-An Chang; Chia-Hsuan Kuan; Chi-Yen Hung; Tai-Chi Chen Wang; Yu-Sheng Chen (Environmental Science and Pollution Research, 2022)
This study aimed to investigate the impact of weather conditions on the daily incidence of the COVID-19 pandemic in late spring 2021 in Taiwan, which is unlike the weather conditions of the COVID-19 outbreak in 2020. Meteorological parameters such as maximum daily temperature, relative humidity, and wind speed were included. The Spearman rank correlation test was used to evaluate the relationship between weather and daily domestic COVID-19 cases. The maximum daily temperature had a positively significant correlation with daily new COVID-19 cases within a 14-day lag period, while the relative humidity and wind speed has a fairly high correlation with the number of daily cases within a 13- and 14-day lag, respectively. In addition, the weather characteristics during this period were an increasingly high temperature, with steady high relative humidity and slightly decreasing wind speed. Our study revealed the weather conditions at the time of the domestic outbreak of COVID-19 in Taiwan in May 2021 and the possible association between weather factors and the COVID-19 pandemic. Further large-scale analysis of weather factors is essential for understanding the impact of weather on the spread of infectious diseases.

Comparative metabolomics reveal the participation of soybean unique rhizosphere metabolites in susceptibility and resistance of host soybean to Phytophthora sojae - Zhuoqun Zhang; Xiangqi Bi; Xiuming Du; Haixu Liu; Tai An; Yifan Zhao; Han Yu; Yufei Chen; Jingzhi Wen (Plant and Soil, 2022)

The influence of climate change on the allocation efficiency of new and tradition energy - Kuei-Ying Huang; Yung-ho Chiu; Tzu-Han Chang; Tai-Yu Lin (Environmental Science and Pollution Research, 2022)

Vitamin D regulates transepithelial acid secretion in zebrafish (Danio rerio) larvae - Chia-Hao Lin; Sian-Tai Liu; Yu-Chun Wang; Yi-Ling Tsou; Huei-Jyun Hu (Frontiers in Marine Science, 2022)
Maintenance of an acid-base balance is essential for normal physiological processes in vertebrates. Freshwater fishes live in an aquatic environment with variable pH, and their buffering capacity for acid-base balance in body fluids is weak. Thus, after acid exposure, fishes secrete excess acid to prevent internal acidosis. Acid-secreting ionocytes present in the adult gills and embryonic skin are primarily responsible for acid secretion, and H + -ATPase and Na + /H + exchanger 3 (NHE3) are the two main transporters responsible for apical acid secretion. Vitamin D is a well-known hormone involved in the maintenance of Ca 2+ homeostasis and is suggested to be involved in acid-base regulation by modulating the activity and/or mRNA expression of NHE3 in mammalian models. It remains unclear whether vitamin D is involved in acid secretion in fishes. The aim of the present study was to use zebrafish as a model to determine whether vitamin D and its receptors influence acid secretion. Our results indicated that the levels of 1α, 25-dihydroxyvitamin D 3 (1α,25(OH) 2 D 3 ), the bioactive vitamin D, were significantly increased in 3 days post-fertilization zebrafish larvae after exposure to acidic freshwater (AFW, pH 4.0). Exogenous 1α,25(OH) 2 D 3 (20 μg/L) incubation substantially enhanced the mRNA expression of acid-secreting transporters and acid secretion at the skin of the entire body and each H + -ATPase-rich cell (HRC), a type of acid-secreting ionocyte. Furthermore, the expression of vitamin D receptors (VDRs) was identified in HRCs of zebrafish. When both VDRa and VDRb were knocked down, acid secretion and the mRNA expression of acid-secreting transporters were significantly decreased. Moreover, double knockdown of VDRa/b prevented the increase in acid secretion induced by AFW and 1α,25(OH) 2 D 3 treatment. This study is the first to indicate that vitamin D is involved in acid secretion in fish.

Influence of vessel upsizing on pollution emissions along Far East–Europe trunk routes - Hui-Huang Tai; Yu-Meng Wang (Environmental Science and Pollution Research, 2022)

Asymmetric Structures of a Squall-Line MCS over Taiwan with Significant Hydraulic Jumps - Yu-Tai Pan; Ming-Jen Yang (Asia-Pacific Journal of Atmospheric Sciences, 2022)
On 19 April 2019, a mature squall-line mesoscale convective system (MCS) with the characteristics of a leading convective line and trailing stratiform landed on Taiwan, resulting in strong gust wind and heavy rainfall. This squall-line MCS became asymmetric after landfall on Taiwan. Two sets of idealized numerical simulations (mountain heights and low-level vertical wind shear) using the Weather Research and Forecasting (WRF) model were conducted to examine the impacts of realistic Taiwan topography on a squall-line MCS. Results showed numerous similarities between the idealized simulations and real-case observations. The low-level Froude number which considered the terrain height (F mt ) was calculated to examine the blocking effect of the Taiwan terrain, and the cold pool (determined by − 1.5 K isotherm) was found to be completely blocked by the 500-m height contour. The northeast-southwest orientation of the Snow Mountain Range (SMR), and the north–south orientation of the Central Mountain Range (CMR) led to the upwind side asymmetry. On the other hand, the lee-side asymmetry was associated with different intensities and occurrence locations of the hydraulic jump between the SMR and southern CMR, and the cold-pool Froude number (F cp ) indicated the flow-regime transition from subcritical to supercritical.

Tracking Neural Stem Cells in vivo: Achievements and Limitations - Chun-Ran Xue; Kan Wang; Meng-Ze Zhang; Ze Wang; Ya-Ying Song; Hao-Jun Yu; Yong Hao; Yang-Tai Guan (Stem Cell Reviews and Reports, 2022)

Tau Toxicity in Neurodegeneration - Shu-Yu Liang; Zuo-Teng Wang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2022)

Whole-Exome Sequencing Identified a Novel Mutation in RNF216 in a Family with Gordon Holmes Syndrome - Ke-Liang Chen; He Wang; Gui-Xian Zhao; Lei Wei; Yu-Yuan Huang; Shi-Dong Chen; Jian Sun; Qiang Dong; Mei Cui; Jin-Tai Yu (Journal of Molecular Neuroscience, 2022)

Downregulated Calcium-Binding Protein S100A16 and HSP27 in Placenta-Derived Multipotent Cells Induce Functional Astrocyte Differentiation - Yu-Che Cheng; Chi-Jung Huang; Wei-Chi Ku; Shu-Lin Guo; Lu-Tai Tien; Yih-Jing Lee; Chih-Cheng Chien (Stem Cell Reviews and Reports, 2022)
Little is known about genes that induce stem cells differentiation into astrocytes. We previously described that heat shock protein 27 (HSP27) downregulation is directly related to neural differentiation under chemical induction in placenta-derived multipotent stem cells (PDMCs). Using this neural differentiation cell model, we cross-compared transcriptomic and proteomic data and selected 26 candidate genes with the same expression trends in both omics analyses. Those genes were further compared with a transcriptomic database derived from Alzheimer’s disease (AD). Eighteen out of 26 candidates showed opposite expression trends between our data and the AD database. The mRNA and protein expression levels of those candidates showed downregulation of HSP27, S100 calcium-binding protein A16 (S100A16) and two other genes in our neural differentiation cell model. Silencing these four genes with various combinations showed that co-silencing HSP27 and S100A16 has stronger effects than other combinations for astrocyte differentiation. The induced astrocyte showed typical astrocytic star-shape and developed with ramified, stringy and filamentous processes as well as differentiated endfoot structures. Also, some of them connected with each other and formed continuous network. Immunofluorescence quantification of various neural markers indicated that HSP27 and S100A16 downregulation mainly drive PDMCs differentiation into astrocytes. Immunofluorescence and confocal microscopic images showed the classical star-like shape morphology and co-expression of crucial astrocyte markers in induced astrocytes, while electrophysiology and Ca 2+ influx examination further confirmed their functional characteristics. In conclusion, co-silencing of S100A16 and HSP27 without chemical induction leads to PDMCs differentiation into functional astrocytes. Graphical abstract

Spatial delineation approach to weather derivatives with three multivariate manners - Ai-Ju Shao; Tai-Yi Yu (Natural Hazards, 2022)

A comparison of atmospheric geochemistry through lichens from volcanic and non-volcanic areas, north Taiwan - Le-Qi Lin; Hsueh-Yu Lu; Ju-Lien Pi; Tai-Sheng Liou; Wen-Fu Chen; Pei-Shan Hsieh (Journal of Earth System Science, 2021)

Faecalicatena faecalis sp. nov., a moderately alkaliphilic bacterial strain isolated from swine faeces - Byeong Seob Oh; Ji-Sun Kim; Seoung Woo Ryu; Seung Yeob Yu; Jung-Sook Lee; Seung-Hwan Park; Se Won Kang; Jiyoung Lee; Mi-Kyung Lee; Kang Hyun Lee; Won Yong Jung; Hyunjung Jung; et al. (Antonie van Leeuwenhoek, 2021)

Three-Dimensional Heterogeneity of Cerebellar Interposed Nucleus-Recipient Zones in the Thalamic Nuclei - Kuang-Yi Ma; Xin-Yu Cai; Xin-Tai Wang; Zhao-Xiang Wang; Wan-Meng Huang; Zhi-Ying Wu; Zhou-Yan Feng; Ying Shen (Neuroscience Bulletin, 2021)

Genomic characterization of a rare Carica papaya X chromosome mutant reveals a candidate monodehydroascorbate reductase 4 gene involved in all-hermaphrodite phenomenon - Jen-Ren Chen; Hiroki Ueno; Hideo Matsumura; Naoya Urasaki; Chen-Yu Lee; Fure-Chyi Chen; Shih-Wen Chin; Chun-Chi Liu; Chan-Tai Chiu; Kazuhiko Tarora; Jing-Yi Li; Chieh Ying Lee; et al. (Molecular Genetics and Genomics, 2021)

Evaluating the energy, health efficiency, and productivity in OECD - Ching-Cheng Lu; Yung-ho Chiu; Chih-Yu Yang; Tai-Yu Lin (Environmental Geochemistry and Health, 2021)

Comparison of Primary Production Using in situ and Satellite-Derived Values at the SEATS Station in the South China Sea - Yung-Yen Shih; Fuh-Kwo Shiah; Chao-Chen Lai; Wen-Chen Chou; Jen-Hua Tai; Yu-Shun Wu; Cheng-Yang Lai; Chia-Ying Ko; Chin-Chang Hung (Frontiers in Marine Science, 2021)
Satellite-based observations of primary production (PP) are broadly used to assess carbon fixation rate of phytoplankton in the global ocean with small spatiotemporal limitations. However, the remote sensing can only reach the ocean surface, the assumption of a PP vertically exponential decrease with increasing depth from the surface to the bottom of euphotic zone may cause a substantial and potential discrepancy between in situ measurements and satellite-based observations of PP. This study compared euphotic zone integrated PP derived from measurements based on ship-based in situ incubation (i.e., PP in situ ) and those derived from the satellite-based vertically generalized production model (VGPM; PP VGPM ) for the period 2003∼2016 at the South East Asian Time-series Study (SEATS) station. PP values obtained during the NE-monsoon (NEM: Nov∼Mar; PP in situ = 323 ± 134; PP VGPM = 443 ± 142 mg-C m –2 d –1 ) were ∼2-fold higher than those recorded during the SW-monsoon (SWM: Apr∼Oct; PP in situ = 159 ± 58; PP VGPM = 250 ± 36 mg-C m –2 d –1 ), regardless of the method used for derivation. The main reason for the higher PP values during the NEM appears to have been a greater abundance of inorganic nutrients were made available by vertical advection. Note that on average, PP in situ estimates were ∼50% lower than PP VGPM estimates, regardless of the monsoon. These discrepancies can be mainly attributed to differences from the euphotic zone depth between satellite-based and in situ measurements. The significantly negative relationship between PP measurements obtained in situ and sea surface temperatures observed throughout this study demonstrates that both methods are effective indicators in estimating PP. Overall, our PP in situ analysis indicates that a warming climate is unfavorable for primary production in low-latitude open ocean ecosystems.

In Vivo Intravascular Pacing Using a Wireless Microscale Stimulator - Parinaz Abiri; Sandra Duarte-Vogel; Tzu-Chieh Chou; Arash Abiri; Varun Gudapati; Alireza Yousefi; Mehrdad Roustaei; Chih-Chiang Chang; Qingyu Cui; Jeffrey J. Hsu; Malcolm Bersohn; Dejan Markovic; et al. (Annals of Biomedical Engineering, 2021)

Associations of Sleep Characteristics with Cerebrospinal Fluid sTREM2 in Cognitively Normal Older Adults: the CABLE Study - He-Ying Hu; Ling-Zhi Ma; Hao Hu; Yan-Lin Bi; Ya-Hui Ma; Xue-Ning Shen; Ya-Nan Ou; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2021)

Dynamic analysis of residential and enterprise water supply and leakage efficiencies - Ying Li; Yung-ho Chiu; Yushan Li; Hongyi Cen; Tai-Yu Lin (Environmental Science and Pollution Research, 2021)

Microglia Biomarkers in Alzheimer’s Disease - Peng-Fei Zhang; Hao Hu; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2021)

Anaerococcus faecalis sp. nov., Isolated from Swine Faeces - Seung Yeob Yu; Byeong Seob Oh; Seoung Woo Ryu; Ji-Sun Kim; Jung-Sook Lee; Seung-Hwan Park; Se Won Kang; Jiyoung Lee; Mi-Kyung Lee; Hanna Choe; Won Yong Jung; Hyunjung Jung; et al. (Current Microbiology, 2021)

Sleep Characteristics and Cerebrospinal Fluid Progranulin in Older Adults: The CABLE Study - Meng Wang; Fu-Rong Sun; Yan-Lin Bi; Ya-Hui Ma; Jian-Jun Yin; Xue-Ning Shen; Xiao-Tong Wang; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2021)

Serum Calcium Predicts Cognitive Decline and Clinical Progression of Alzheimer’s Disease - Ling-Zhi Ma; Zi-Xuan Wang; Zuo-Teng Wang; Xiao-He Hou; Xue-Ning Shen; Ya-Nan Ou; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2021)

Efficiency assessment of coal energy and non-coal energy under bound dynamic DDF DEA - Ying Li; Tai-Yu Lin; Yung-ho Chiu; Hongyi Cen; Yi-Nuo Lin (Environmental Science and Pollution Research, 2021)

Effectiveness of Adding Antiplatelets to Oral Anticoagulants in Patients with Acute Ischemic Stroke with Atrial Fibrillation and Concomitant Large Artery Steno-Occlusion - Joon-Tae Kim; Ji Sung Lee; Beom Joon Kim; Jong-Moo Park; Kyusik Kang; Soo Joo Lee; Jae Guk Kim; Jae-Kwan Cha; Dae-Hyun Kim; Tai Hwan Park; Sang-Soon Park; Kyung Bok Lee; et al. (Translational Stroke Research, 2020)

High-precision downward continuation of potential fields algorithm utilizing adaptive damping coefficient of generalized minimal residuals - Zhi-Hou Zhang; Xiao-Long Liao; Ze-Yu Shi; Anthony R. Lowry; Yu Yao; Run-Qi Lu; Xiang-Tai Fan; Peng-Fei Liu; Si-Wei Zhao (Applied Geophysics, 2020)

Optimizing the MIC breakpoints of amoxicillin and tetracycline for antibiotic selection in the rescue therapy of H. pylori with bismuth quadruple regimen - Ming-Tsung Hsieh; Wei-Lun Chang; Chung-Tai Wu; Hsiao-Bai Yang; Hsin-Yu Kuo; Meng-Ying Lin; Hsiu-Chi Cheng; Yu-Chin Tsai; Bor-Shyang Sheu (European Journal of Clinical Pharmacology, 2020)

Infusion of Human Mesenchymal Stem Cells Improves Regenerative Niche in Thioacetamide-Injured Mouse Liver - Ying-Hsien Kao; Yu-Chun Lin; Po-Huang Lee; Chia-Wei Lin; Po-Han Chen; Tzong-Shyuan Tai; Yo-Chen Chang; Ming-Huei Chou; Chih-Yang Chang; Cheuk-Kwan Sun (Tissue Engineering and Regenerative Medicine, 2020)

Association of Polygenic Risk Score with Age at Onset and Cerebrospinal Fluid Biomarkers of Alzheimer’s Disease in a Chinese Cohort - Wei-Wei Li; Zhen Wang; Dong-Yu Fan; Ying-Ying Shen; Dong-Wan Chen; Hui-Yun Li; Ling Li; Heng Yang; Yu-Hui Liu; Xian-Le Bu; Wang-Sheng Jin; Fan Zeng; et al. (Neuroscience Bulletin, 2020)

Risk perception and response toward climate change for higher education students in Taiwan - Tai-Kuei Yu; Joseph P. Lavallee; Bruno Di Giusto; I-Cheng Chang; Tai-Yi Yu (Environmental Science and Pollution Research, 2020)

Reversal of Social Recognition Deficit in Adult Mice with MECP2 Duplication via Normalization of MeCP2 in the Medial Prefrontal Cortex - Bin Yu; Bo Yuan; Jian-Kun Dai; Tian-lin Cheng; Sheng-Nan Xia; Ling-Jie He; Yi-Ting Yuan; Yue-Fang Zhang; Hua-Tai Xu; Fu-Qiang Xu; Zhi-Feng Liang; Zi-Long Qiu (Neuroscience Bulletin, 2020)

The evaluation of BTEX and carbonyls emissions from recycled building materials - Yu-Hsiang Cheng; Chi-Chi Lin; Yun-Tai Lee; Yu-Chun Lin (Environmental Monitoring and Assessment, 2020)

Serum Uric Acid Levels and Risk of Intracranial Atherosclerotic Stenosis: A Cross-Sectional Study - Lin Li; Jun-Xia Zhu; Xiao-He Hou; Ya-Hui Ma; Wei Xu; Chen-Chen Tan; Fu-Rong Sun; Hong-Qi Li; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Structural genome analysis in cultivated potato taxa - Maria Kyriakidou; Sai Reddy Achakkagari; José Héctor Gálvez López; Xinyi Zhu; Chen Yu Tang; Helen H. Tai; Noelle L. Anglin; David Ellis; Martina V. Strömvik (Theoretical and Applied Genetics, 2020)
Key message Twelve potato accessions were selected to represent two principal views on potato taxonomy. The genomes were sequenced and analyzed for structural variation (copy number variation) against three published potato genomes. Abstract The common potato ( Solanum tuberosum L.) is an important staple crop with a highly heterozygous and complex tetraploid genome. The other taxa of cultivated potato contain varying ploidy levels (2 X –5 X ), and structural variations are common in the genomes of these species, likely contributing to the diversification or agronomic traits during domestication. Increased understanding of the genomes and genomic variation will aid in the exploration of novel agronomic traits. Thus, sequencing data from twelve potato landraces, representing the four ploidy levels, were used to identify structural genomic variation compared to the two currently available reference genomes, a double monoploid potato genome and a diploid inbred clone of S. chacoense . The results of a copy number variation analysis showed that in the majority of the genomes, while the number of deletions is greater than the number of duplications, the number of duplicated genes is greater than the number of deleted ones. Specific regions in the twelve potato genomes have a high density of CNV events. Further, the auxin-induced SAUR genes (involved in abiotic stress), disease resistance genes and the 2-oxoglutarate/Fe(II)-dependent oxygenase superfamily proteins, among others, had increased copy numbers in these sequenced genomes relative to the references.

Common Variant in TREM1 Influencing Brain Amyloid Deposition in Mild Cognitive Impairment and Alzheimer’s Disease - Yue-Song Liu; Wen-Jing Yan; Chen-Chen Tan; Jie-Qiong Li; Wei Xu; Xi-Peng Cao; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Elevated Hs-CRP Levels Are Associated with Higher Risk of Intracranial Arterial Stenosis - Bing-Jie Su; Yi Dong; Chen-Chen Tan; Xiao-He Hou; Wei Xu; Fu-Rong Sun; Mei Cui; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Performance Evaluation of a New Mobile POC Lipids Analyzer - Shi-Yann Cheng; Tung-Meng Tsai; Yen-Yu Chen; Po-Jung Lai; Tai-I Chen; Tsai-Jung Chen; Chieh-Hsiao Chen (Journal of Medical and Biological Engineering, 2020)

Mobile Health for Diagnosis-PixoTest HbA1c POCT System - Shi-Yann Cheng; Tung-Meng Tsai; Yen-Yu Chen; Po-Jung Lai; Tai-I Chen; Chiung-Wen Hsu; Chieh-Hsiao Chen (Journal of Medical and Biological Engineering, 2020)

Genome-Wide Association Study of Cerebral Microbleeds on MRI - Hong-Qi Li; Wen-Jie Cai; Xiao-He Hou; Mei Cui; Lan Tan; Jin-Tai Yu; Qiang Dong (Neurotoxicity Research, 2020)

Correlation between TERT C228T and clinic-pathological features in pediatric papillary thyroid carcinoma - Jiangqiao Geng; Yuanhu Liu; Yongli Guo; Huanmin Wang; Jun Tai; Yaqiong Jin; Jie Zhang; Yongbo Yu; Shengcai Wang; Yingluan Song; Xin Ni (Science China Life Sciences, 2019)

Remote Sensing for Detecting Changes of Land Use in Taipei City, Taiwan - Li Chen; Hsiao-Yu Wang; Tai-Sheng Wang; Chang-Huan Kou (Journal of the Indian Society of Remote Sensing, 2019)

Application of Escherichia coli antibiotic resistance patterns for contamination source identification in watershed - Tai-Yi Yu; Ching-Ju Monica Chin; Yu-Jie Chang (Environmental Science and Pollution Research, 2019)

Hydro-mechanical response with respect to the air ventilation for water filtration in homogeneous soil - Wei-Lin Lee; Yih-Chin Tai; Chjeng-Lun Shieh; Kuniaki Miyamoto; Yu-Feng Lin (Journal of Mountain Science, 2019)

Autonomic modulation following an acute bout of bench press with and without blood flow restriction - Yu Lun Tai; Erica M. Marshall; Alaina Glasgow; Jason C. Parks; Leslie Sensibello; J. Derek Kingsley (European Journal of Applied Physiology, 2019)

Canned food intake and urinary bisphenol a concentrations: a randomized crossover intervention study - Chiung-Yu Peng; Eing-Mei Tsai; Tzu-Hsiung Kao; Tai-Cheng Lai; Shih-Shin Liang; Chien-Chih Chiu; Tsu-Nai Wang (Environmental Science and Pollution Research, 2019)

Ginsenoside compound-K inhibits the activity of B cells through inducing IgD-B cell receptor endocytosis in mice with collagen-induced arthritis - Mei Zhang; Shanshan Hu; Juan Tao; Weijie Zhou; Rui Wang; Yu Tai; Feng Xiao; Qingtong Wang; Wei Wei (Inflammopharmacology, 2019)

A pro-environmental behavior model for investigating the roles of social norm, risk perception, and place attachment on adaptation strategies of climate change - Tai-Kuei Yu; Yu-Jie Chang; I-Cheng Chang; Tai-Yi Yu (Environmental Science and Pollution Research, 2019)

Neuroligins Differentially Mediate Subtype-Specific Synapse Formation in Pyramidal Neurons and Interneurons - Qiang-Qiang Xia; Jing Xu; Tai-Lin Liao; Jie Yu; Lei Shi; Jun Xia; Jian-Hong Luo; Junyu Xu (Neuroscience Bulletin, 2019)

Collective responsibility framing also leads to mitigation behavior in East Asia: a replication study in Taiwan - Joseph P. Lavallee; Bruno Di Giusto; Tai-Yi Yu (Climatic Change, 2019)

Correction to: Trichostatin A, a histone deacetylase inhibitor, induces synergistic cytotoxicity with chemotherapy via suppression of Raf/MEK/ERK pathway in urothelial carcinoma - Wei-Chou Lin; Fu-Shun Hsu; Kuan-Lin Kuo; Shing-Hwa Liu; Chia-Tung Shun; Chung-Sheng Shi; Hong-Chiang Chang; Yu-Chieh Tsai; Ming-Chieh Lin; June-Tai Wu; Yu Kuo; Po-Ming Chow; et al. (Journal of Molecular Medicine, 2019)

Effects of aerobic exercise on sad emotion regulation in young women: an electroencephalograph study - Ren-Jen Hwang; Hsin-Ju Chen; Zhan-Xian Guo; Yu-Sheun Lee; Tai-Ying Liu (Cognitive Neurodynamics, 2019)

A Genome-Wide Association Study of α-Synuclein Levels in Cerebrospinal Fluid - Xiao-ling Zhong; Jie-Qiong Li; Li Sun; Ya-Qing Li; Hui-Fu Wang; Xi-Peng Cao; Chen-Chen Tan; Ling Wang; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2019)

Trichostatin A, a histone deacetylase inhibitor, induces synergistic cytotoxicity with chemotherapy via suppression of Raf/MEK/ERK pathway in urothelial carcinoma - Wei-Chou Lin; Fu-Shun Hsu; Kuan-Lin Kuo; Shing-Hwa Liu; Chia-Tung Shun; Chung-Sheng Shi; Hong-Chiang Chang; Yu-Chieh Tsai; Ming-Chieh Lin; June-Tai Wu; Yu Kuo; Po-Ming Chow; et al. (Journal of Molecular Medicine, 2018)

Proteomic discovery of H2O2 response in roots and functional characterization of PutGLP gene from alkaligrass - Juanjuan Yu; Yongxue Zhang; Junming Liu; Lin Wang; Panpan Liu; Zepeng Yin; Siyi Guo; Jun Ma; Zhuang Lu; Tai Wang; Yimin She; Yuchen Miao; et al. (Planta, 2018)

Clearance of Amyloid Beta and Tau in Alzheimer’s Disease: from Mechanisms to Therapy - Shu-Hui Xin; Lin Tan; Xipeng Cao; Jin-Tai Yu; Lan Tan (Neurotoxicity Research, 2018)

Elatostema brachyodontum subsp. lengshuiheensis (Urticaceae), a new subspecies from Guizhou, China - Yun Lin; Ming-Tai An; Zhi-Rong Yang; Yan-Qiang Dai; Deng-Li Yu (Kew Bulletin, 2018)

3D FEM simulation of responses of LWD multi-mode resistivity imaging sonde - Zheng-Ming Kang; Shi-Zhen Ke; Xin Li; Jin-Tai Mi; Wei-Ning Ni; Ming-Yu Li (Applied Geophysics, 2018)

Segmentation by domestic visitor motivation: Changbai Mountain Biosphere Reserve, China - Xiao-ping Gu; Bernard J. Lewis; Li-jun Niu; Da-pao Yu; Li Zhou; Wang-ming Zhou; Zhen-cai Gong; Zhi-juan Tai; Li-min Dai (Journal of Mountain Science, 2018)

Protein-bounded uremic toxin p-cresylsulfate induces vascular permeability alternations - Wei-Hua Tang; Chao-Ping Wang; Teng-Hung Yu; Pei-Yang Tai; Shih-Shin Liang; Wei-Chin Hung; Cheng-Ching Wu; Sung-Hao Huang; Yau-Jiunn Lee; Shih-Chieh Chen (Histochemistry and Cell Biology, 2018)

Treatment outcome of non-carbapenemase-producing carbapenem-resistant Klebsiella pneumoniae infections: a multicenter study in Taiwan - Chin-Fang Su; Chien Chuang; Yi-Tsung Lin; Yu-Jiun Chan; Jung-Chung Lin; Po-Liang Lu; Ching-Tai Huang; Jann-Tay Wang; Yin-Ching Chuang; L. Kristopher Siu; Chang-Phone Fung (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Impacts of hydrogeological characteristics on groundwater-level changes induced by earthquakes - Ching-Yi Liu; Yeeping Chia; Po-Yu Chuang; Yung-Chia Chiu; Tai-Lin Tseng (Hydrogeology Journal, 2018)

Investigating the composition characteristics of dissolved and particulate/colloidal organic matter in effluent-dominated stream using fluorescence spectroscopy combined with multivariable analysis - Min-Da Yu; Xiao-Song He; Bei-Dou Xi; Ru-Tai Gao; Xian-Wei Zhao; Hui Zhang; Cai-Hong Huang; Wenbing Tan (Environmental Science and Pollution Research, 2018)

Different behavioral, neural and neuropeptide responses of fathers to their own and to alien pups in mandarin voles - Wei Yuan; Xiang-Ping Yang; Peng Yu; Rui Jia; Fa-Dao Tai; Bin Wei; Xiao Liu; Lei-Ge Ma (Journal of Comparative Physiology A, 2018)

Soma Detection in 3D Images of Neurons using Machine Learning Technique - Guan-Wei He; Ting-Yuan Wang; Ann-Shyn Chiang; Yu-Tai Ching (Neuroinformatics, 2018)

Spreading of Pathology in Alzheimer’s Disease - Zhong-Yue Lv; Chen-Chen Tan; Jin-Tai Yu; Lan Tan (Neurotoxicity Research, 2017)

A Mitocentric View of Alzheimer’s Disease - Hao Hu; Chen-Chen Tan; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Associations of rs3740677 within GAB2 Gene with LOAD in Chinese Han Population - Jing-Yu Zheng; Hui-Fu Wang; Yu Wan; Meng-Shan Tan; Chen-Chen Tan; Lin Tan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Effects of HLA-DRB1/DQB1 Genetic Variants on Neuroimaging in Healthy, Mild Cognitive Impairment, and Alzheimer’s Disease Cohorts - Zi-Xuan Wang; Hui-Fu Wang; Lin Tan; Jinyuan Liu; Yu Wan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Genetic Association of HLA Gene Variants with MRI Brain Structure in Alzheimer’s Disease - Zi-Xuan Wang; Yu Wan; Lin Tan; Jinyuan Liu; Hui-Fu Wang; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Association of DISC1 Polymorphisms with Late-Onset Alzheimer’s Disease in Northern Han Chinese - Xiao-Yan Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Ling-Li Kong; Zhan-Jie Zheng; Chen-Chen Tan; Wei Zhang; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; et al. (Molecular Neurobiology, 2017)

HLA-A2 Alleles Mediate Alzheimer’s Disease by Altering Hippocampal Volume - Zi-Xuan Wang; Hui-Fu Wang; Lin Tan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

SORL1 Is Associated with the Risk of Late-Onset Alzheimer’s Disease: a Replication Study and Meta-Analyses - Cheng-Cheng Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Influence of 15N-labeled ammonium sulfate and straw on nitrogen retention and supply in different fertility soils - Fei-Fei Pan; Wan-Tai Yu; Qiang Ma; Hua Zhou; Chun-Ming Jiang; Yong-Gang Xu; Jin-Feng Ren (Biology and Fertility of Soils, 2017)

Geochemistry, geochronology, and petrogenesis of mid-Cretaceous Talabuco volcanic rocks, central Tibet: implications for the evolution of the Bangong Meso-Tethys - Xi-Chong Hu; Bin Xia; Qiang-Tai Huang; Wei-Liang Liu; Yun Zhong; Ya-Juan Yuan; Lian-Ze Xia; Yu Wu; Xiao Zhang (International Geology Review, 2017)

Endovascular Treatment Versus Intravenous Thrombolysis for Acute Ischemic Stroke: a Quantitative Review and Meta-Analysis of 21 Randomized Trials - Chen-Chen Tan; Hui-Fu Wang; Jin-Long Ji; Meng-Shan Tan; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

PGRN Is Associated with Late-Onset Alzheimer’s Disease: a Case–Control Replication Study and Meta-analysis - Hui-Min Xu; Lin Tan; Yu Wan; Meng-Shan Tan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Impacts of CD33 Genetic Variations on the Atrophy Rates of Hippocampus and Parahippocampal Gyrus in Normal Aging and Mild Cognitive Impairment - Wen-Ying Wang; Ying Liu; Hui-Fu Wang; Lin Tan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

A Missense Variant in TREML2 Reduces Risk of Alzheimer’s Disease in a Han Chinese Population - Teng Jiang; Yu Wan; Jun-Shan Zhou; Meng-Shan Tan; Qing Huang; Xi-Chen Zhu; Huan Lu; Hui-Fu Wang; Qi Chen; Lin Tan; Ying-Dong Zhang; Lan Tan; et al. (Molecular Neurobiology, 2017)

TREM2 Overexpression has No Improvement on Neuropathology and Cognitive Impairment in Aging APPswe/PS1dE9 Mice - Teng Jiang; Yu Wan; Ying-Dong Zhang; Jun-Shan Zhou; Qing Gao; Xi-Chen Zhu; Jian-Quan Shi; Huan Lu; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Effect of CR1 Genetic Variants on Cerebrospinal Fluid and Neuroimaging Biomarkers in Healthy, Mild Cognitive Impairment and Alzheimer's Disease Cohorts - Xi-Chen Zhu; Hui-Fu Wang; Teng Jiang; Huan Lu; Meng-Shan Tan; Chen-Chen Tan; Lin Tan; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Association of Parkinson’s Disease GWAS-Linked Loci with Alzheimer’s Disease in Han Chinese - Xi-Chen Zhu; Lei Cao; Meng-Shan Tan; Teng Jiang; Hui-Fu Wang; Huan Lu; Chen-Chen Tan; Wei Zhang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

GWAS-Linked Loci and Neuroimaging Measures in Alzheimer’s Disease - Jie-Qiong Li; Hui-Fu Wang; Xi-Chen Zhu; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

The Impact of UNC5C Genetic Variations on Neuroimaging in Alzheimer’s Disease - Jia-Hao Sun; Hui-Fu Wang; Xi-Chen Zhu; Wan-Jiang Yu; Chen-Chen Tan; Teng Jiang; Meng-Shan Tan; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2016)

Association of Single-Nucleotide Polymorphism in ANK1 with Late-Onset Alzheimer’s Disease in Han Chinese - Song Chi; Jing-Hui Song; Meng-Shan Tan; Wei Zhang; Zi-Xuan Wang; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2016)

Dietary Patterns and Risk of Dementia: a Systematic Review and Meta-Analysis of Cohort Studies - Lei Cao; Lan Tan; Hui-Fu Wang; Teng Jiang; Xi-Chen Zhu; Huan Lu; Meng-Shan Tan; Jin-Tai Yu (Molecular Neurobiology, 2016)

Frontotemporal Lobar Degeneration: Mechanisms and Therapeutic Strategies - Ya-Qing Li; Meng-Shan Tan; Jin-Tai Yu; Lan Tan (Molecular Neurobiology, 2016)

The Role of Reelin Signaling in Alzheimer’s Disease - Nan-Nan Yu; Meng-Shan Tan; Jin-Tai Yu; An-Mu Xie; Lan Tan (Molecular Neurobiology, 2016)

The Role of MAPT in Neurodegenerative Diseases: Genetics, Mechanisms and Therapy - Cheng-Cheng Zhang; Ang Xing; Meng-Shan Tan; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2016)

Multiple Effect of APOE Genotype on Clinical and Neuroimaging Biomarkers Across Alzheimer’s Disease Spectrum - Ying Liu; Lan Tan; Hui-Fu Wang; Yong Liu; Xiao-Ke Hao; Chen-Chen Tan; Teng Jiang; Bing Liu; Dao-Qiang Zhang; Jin-Tai Yu (Molecular Neurobiology, 2016)

Impact of Common Variations in PLD3 on Neuroimaging Phenotypes in Non-demented Elders - Chong Wang; Hui-Fu Wang; Meng-Shan Tan; Ying Liu; Teng Jiang; Dao-Qiang Zhang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2016)

The Role of Cdk5 in Alzheimer’s Disease - Shu-Lei Liu; Chong Wang; Teng Jiang; Lan Tan; Ang Xing; Jin-Tai Yu (Molecular Neurobiology, 2016)

Two-Point Stretchable Electrode Array for Endoluminal Electrochemical Impedance Spectroscopy Measurements of Lipid-Laden Atherosclerotic Plaques - René R. Sevag Packard; XiaoXiao Zhang; Yuan Luo; Teng Ma; Nelson Jen; Jianguo Ma; Linda L. Demer; Qifa Zhou; James W. Sayre; Rongsong Li; Yu-Chong Tai; Tzung K. Hsiai (Annals of Biomedical Engineering, 2016)

The Role of Retromer in Alzheimer’s Disease - Qiu-Yue Zhang; Meng-Shan Tan; Jin-Tai Yu; Lan Tan (Molecular Neurobiology, 2016)

The Role of PGRN in Alzheimer’s Disease - Hua Jing; Meng-Shan Tan; Jin-Tai Yu; Lan Tan (Molecular Neurobiology, 2016)

The Role of TDP-43 in Alzheimer’s Disease - Xiao-Long Chang; Meng-Shan Tan; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2016)

Education and Risk of Dementia: Dose-Response Meta-Analysis of Prospective Cohort Studies - Wei Xu; Lan Tan; Hui-Fu Wang; Meng-Shan Tan; Lin Tan; Jie-Qiong Li; Qing-Fei Zhao; Jin-Tai Yu (Molecular Neurobiology, 2016)

Curcumin downregulates p38 MAPK-dependent X-ray repair cross-complement group 1 (XRCC1) expression to enhance cisplatin-induced cytotoxicity in human lung cancer cells - Chun-Liang Tung; Yi-Jun Jian; Jyh-Cheng Chen; Tai-Jing Wang; Wen-Ching Chen; Hao-Yu Zheng; Po-Yuan Chang; Kai-Sheng Liao; Yun-Wei Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Paleoclimatic record from Chumbur-Kosa section in Sea of Azov region since Marine Isotope Stage 11 - Ye Liang; Tai-bao Yang; Andrey Aleksevitch Velichko; Biao Zeng; Pei-hong Shi; Lin-dong Wang; Yi He; Jie Chen; Yu Chen (Journal of Mountain Science, 2016)

Angiotensin-(1-7) is Reduced and Inversely Correlates with Tau Hyperphosphorylation in Animal Models of Alzheimer’s Disease - Teng Jiang; Ying-Dong Zhang; Jun-Shan Zhou; Xi-Chen Zhu; You-Yong Tian; Hong-Dong Zhao; Huan Lu; Qing Gao; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2016)

The Essential Role of Soluble Aβ Oligomers in Alzheimer’s Disease - Zi-Xuan Wang; Lan Tan; Jinyuan Liu; Jin-Tai Yu (Molecular Neurobiology, 2016)

Identification of Microalgae by Laser Desorption/Ionization Mass Spectrometry Coupled with Multiple Nanomatrices - Lung-Hsiang Peng; Binesh Unnikrishnan; Chi-Yu Shih; Tung-Ming Hsiung; Jeng Chang; Pang-Hung Hsu; Tai-Chia Chiu; Chih-Ching Huang (Marine Biotechnology, 2016)

Pathogenesis and Therapeutic Strategies in Alzheimer’s Disease: From Brain to Periphery - Jin-Tai Yu; Can Zhang (Neurotoxicity Research, 2016)

Development of single-chain variable fragments (scFv) against influenza virus targeting hemagglutinin subunit 2 (HA2) - Tai-Wei Li; Shu-Fang Cheng; Yen-Tzu Tseng; Yu-Chih Yang; Wen-chun Liu; Sheng-Cyuan Wang; Mei-Ju Chou; Yu-Jen Lin; Yueh Wang; Pei-Wen Hsiao; Suh-Chin Wu; Ding-Kwo Chang (Archives of Virology, 2016)

Roles of microRNA-1 in hypoxia-induced apoptotic insults to neuronal cells - Chia-Yu Chang; Tai-Ngar Lui; Jia-Wei Lin; Yi-Ling Lin; Chung-Hsi Hsing; Jhi-Joung Wang; Ruei-Ming Chen (Archives of Toxicology, 2016)

Overexpression of a phospholipase Dα gene from Ammopiptanthus nanus enhances salt tolerance of phospholipase Dα1-deficient Arabidopsis mutant - Hao Qiang Yu; Tai Ming Yong; Hong Jie Li; Yan Ping Liu; Shu Feng Zhou; Feng Ling Fu; Wan Chen Li (Planta, 2015)

Brain-Derived Neurotrophic Factor in Alzheimer’s Disease: Risk, Mechanisms, and Therapy - Jing-Hui Song; Jin-Tai Yu; Lan Tan (Molecular Neurobiology, 2015)

The Role of PICALM in Alzheimer’s Disease - Wei Xu; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2015)

Chronic Metformin Preconditioning Provides Neuroprotection via Suppression of NF-κB-Mediated Inflammatory Pathway in Rats with Permanent Cerebral Ischemia - Xi-Chen Zhu; Teng Jiang; Qiao-Quan Zhang; Lei Cao; Meng-Shan Tan; Hui-Fu Wang; Zheng-Zheng Ding; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2015)

Induced Pluripotent Stem Cells for Disease Modeling and Drug Discovery in Neurodegenerative Diseases - Lei Cao; Lan Tan; Teng Jiang; Xi-Chen Zhu; Jin-Tai Yu (Molecular Neurobiology, 2015)

Cloning and functional validation of molybdenum cofactor sulfurase gene from Ammopiptanthus nanus - Hao Qiang Yu; Yuan Yuan Zhang; Tai Ming Yong; Yan Ping Liu; Shu Feng Zhou; Feng Ling Fu; Wan Chen Li (Plant Cell Reports, 2015)

The soybean gene, GmMYBJ2, encodes a R2R3-type transcription factor involved in drought stress tolerance in Arabidopsis thaliana - Lian-Tai Su; Ying Wang; De-Quan Liu; Xiao-Wei Li; Ying Zhai; Xin Sun; Xu-Yan Li; Ya-Jing Liu; Jing-Wen Li; Qing-Yu Wang (Acta Physiologiae Plantarum, 2015)

Axonal Transport Defects in Alzheimer’s Disease - Zi-Xuan Wang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2015)

MS4A Cluster in Alzheimer’s Disease - Jing Ma; Jin-Tai Yu; Lan Tan (Molecular Neurobiology, 2015)

Causes and Consequences of MicroRNA Dysregulation in Neurodegenerative Diseases - Lin Tan; Jin-Tai Yu; Lan Tan (Molecular Neurobiology, 2015)

ABCA7 in Alzheimer’s Disease - Qing-Fei Zhao; Jin-Tai Yu; Meng-Shan Tan; Lan Tan (Molecular Neurobiology, 2015)

The Role of Cholesterol Metabolism in Alzheimer’s Disease - Jia-Hao Sun; Jin-Tai Yu; Lan Tan (Molecular Neurobiology, 2015)

The Role of SORL1 in Alzheimer’s Disease - Rui-Hua Yin; Jin-Tai Yu; Lan Tan (Molecular Neurobiology, 2015)

Using fluorescence spectroscopy coupled with chemometric analysis to investigate the origin, composition, and dynamics of dissolved organic matter in leachate-polluted groundwater - Xiao-Song He; Bei-Dou Xi; Ru-Tai Gao; Lei Wang; Yan Ma; Dong-Yu Cui; Wen-Bing Tan (Environmental Science and Pollution Research, 2015)

TYROBP in Alzheimer’s Disease - Jing Ma; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2015)

PLD3 in Alzheimer’s Disease - Jun Wang; Jin-Tai Yu; Lan Tan (Molecular Neurobiology, 2015)

CR1 in Alzheimer's Disease - Xi-Chen Zhu; Jin-Tai Yu; Teng Jiang; Ping Wang; Lei Cao; Lan Tan (Molecular Neurobiology, 2015)

Effects of Single and Double Bonds in Linkers on Colorimetric and Fluorescent Sensing Properties of Polyving Akohol Grafting Rhodamine Hydrazides - Tong-Mou Geng; Xie Wang; Zhu-Qing Wang; Tai-Jie Chen; Hai Zhu; Yu Wang (Journal of Fluorescence, 2015)

Ischemic Preconditioning Provides Neuroprotection by Induction of AMP-Activated Protein Kinase-Dependent Autophagy in a Rat Model of Ischemic Stroke - Teng Jiang; Jin-Tai Yu; Xi-Chen Zhu; Qiao-Quan Zhang; Meng-Shan Tan; Lei Cao; Hui-Fu Wang; Jian-Quan Shi; Li Gao; Hao Qin; Ying-Dong Zhang; Lan Tan (Molecular Neurobiology, 2015)

Cognitive Reserve and Alzheimer’s Disease - Wei Xu; Jin-Tai Yu; Meng-Shan Tan; Lan Tan (Molecular Neurobiology, 2015)

Endoplasmic Reticulum Dysfunction in Alzheimer’s Disease - Jie-Qiong Li; Jin-Tai Yu; Teng Jiang; Lan Tan (Molecular Neurobiology, 2015)

S-Nitrosylation in Alzheimer's disease - Qing-Fei Zhao; Jin-Tai Yu; Lan Tan (Molecular Neurobiology, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Establishment of a structural equation model for ground-level ozone: a case study at an urban roadside site - Kun-Ming Lin; Tai-Yi Yu; Len-Fu Chang (Environmental Monitoring and Assessment, 2014)

The effects of Typhoon Morakot on concentration of airborne particulates derived from unvegetated riverbanks - Kun-Ming Lin; Wang-Kun Chen; Tai-Yi Yu; Len-Fu Chang (Natural Hazards, 2014)

Spatial distribution of soil erosion and suspended sediment transport rate for Chou-Shui river basin - Chin-Ping Lin; Ching-Nuo Chen; Yu-Min Wang; Chih-Heng Tsai; Chang-Tai Tsai (Journal of Earth System Science, 2014)

Submicron particle characteristics of atmospheres in a long highway tunnel - Mei-Yin Hwa; Tai-Yi Yu (Environmental Monitoring and Assessment, 2014)

A Stochastic Approach for Seasonal Water-Shortage Probability Forecasting Based on Seasonal Weather Outlook - Pao-Shan Yu; Tao-Chang Yang; Chen-Min Kuo; Yi-Tai Wang (Water Resources Management, 2014)

Mutations in Ralstonia solanacearum loci involved in lipopolysaccharide biogenesis, phospholipid trafficking and peptidoglycan recycling render bacteriophage infection - Yu-Hau Hong; Chi Huang; Kuan-Chung Wang; Tai-Hsiang Chu; Chien-Hui Li; Yu-Ju Chu; Chiu-Ping Cheng (Archives of Microbiology, 2014)

Quantitative trait loci analysis of individual and total isoflavone contents in soybean seeds - HAI JUN ZHANG; JING WEN LI; YA JING LIU; WEN ZHU JIANG; XING LIN DU; LIN LI; XIAO WEI Li; LIAN TAI SU; QING YU WANG; YING WANG (Journal of Genetics, 2014)

Development of real-world driving cycles and estimation of emission factors for in-use light-duty gasoline vehicles in urban areas - Mei-Yin Hwa; Tai-Yi Yu (Environmental Monitoring and Assessment, 2014)

CD33 in Alzheimer's Disease - Teng Jiang; Jin-Tai Yu; Nan Hu; Meng-Shan Tan; Xi-Chen Zhu; Lan Tan (Molecular Neurobiology, 2014)

C9ORF72 Mutations in Neurodegenerative Diseases - Ying Liu; Jin-Tai Yu; Yu Zong; Jing Zhou; Lan Tan (Molecular Neurobiology, 2014)

Targeting the mTOR Signaling Network for Alzheimer’s Disease Therapy - Chong Wang; Jin-Tai Yu; Dan Miao; Zhong-Chen Wu; Meng-Shan Tan; Lan Tan (Molecular Neurobiology, 2014)

Age-dependent association of KIBRA gene polymorphism with Alzheimer’s disease in Han Chinese - Hui-Fu Wang; Lan Tan; Jin-Tai Yu; Xiao-Ying Ma; Qiu-Yan Liu; Wei Wang (Molecular Biology Reports, 2013)

The NLRP3 Inflammasome in Alzheimer’s Disease - Meng-Shan Tan; Jin-Tai Yu; Teng Jiang; Xi-Chen Zhu; Lan Tan (Molecular Neurobiology, 2013)

β-Arrestins as Potential Therapeutic Targets for Alzheimer’s Disease - Teng Jiang; Jin-Tai Yu; Meng-Shan Tan; Xi-Chen Zhu; Lan Tan (Molecular Neurobiology, 2013)

Autophagy Modulation for Alzheimer’s Disease Therapy - Xi-Chen Zhu; Jin-Tai Yu; Teng Jiang; Lan Tan (Molecular Neurobiology, 2013)

Emodin can induce K562 cells to erythroid differentiation and improve the expression of globin genes - Yan-Ni Ma; Ming-Tai Chen; Zhi-Kui Wu; Hua-Lu Zhao; Hai-Chuan Yu; Jia Yu; Jun-Wu Zhang (Molecular and Cellular Biochemistry, 2013)

Diagnosis and testing of low-level cloud parameterizations for the NCEP/GFS model using satellite and ground-based measurements - Hyelim Yoo; Zhanqing Li; Yu-Tai Hou; Steve Lord; Fuzhong Weng; Howard W. Barker (Climate Dynamics, 2013)

TREM2 in Alzheimer’s disease - Teng Jiang; Jin-Tai Yu; Xi-Chen Zhu; Lan Tan (Molecular Neurobiology, 2013)

Identification of source regions of PM10 with backward trajectory-based statistical models during PM10 episodes - Tai-Yi Yu (Environmental Monitoring and Assessment, 2013)

Optimizing cadmium and mercury specificity of CadR-based E. coli biosensors by redesign of CadR - Hu-Chun Tao; Zhi-Wen Peng; Peng-Song Li; Tai-An Yu; Jie Su (Biotechnology Letters, 2013)

Dynamic analysis for gene expression profiles of endothelial colony forming cells under hypoxia - De-Cai Yu; Wen-Du Feng; Xian-Biao Shi; Zhi-Yong Wang; Wei Ge; Chun-Ping Jiang; Xi-Tai Sun; Yi-Tao Ding (Genes & Genomics, 2013)

Erratum to: The impacts of coordinative exercise on executive function in kindergarten children: an ERP study - Yu-Kai Chang; Yu-Jung Tsai; Tai-Ting Chen; Tsung-Min Hung (Experimental Brain Research, 2013)

Association of TOMM40 Polymorphisms with Late-Onset Alzheimer’s Disease in a Northern Han Chinese Population - Xiao-Ying Ma; Jin-Tai Yu; Wei Wang; Hui-Fu Wang; Qiu-Yan Liu; Wei Zhang; Lan Tan (NeuroMolecular Medicine, 2013)

A novel antitubulin agent, DPQZ, induces cell apoptosis in human oral cancer cells through Ras/Raf inhibition and MAP kinases activation - Mann-Jen Hour; Kun-Tsung Lee; Yang-Chang Wu; Chi-Yu Wu; Bang-Jau You; Tai-Lin Chen; Hong-Zin Lee (Archives of Toxicology, 2013)

Computer Aided Alignment and Quantitative 4D Structural Plasticity Analysis of Neurons - Ping-Chang Lee; Hai-yan He; Chih-Yang Lin; Yu-Tai Ching; Hollis T. Cline (Neuroinformatics, 2013)

The enhancement of biofilm formation in Group B streptococcal isolates at vaginal pH - Yueh-Ren Ho; Chien-Ming Li; Chen-Hsiang Yu; Yuh-Jyh Lin; Ching-Ming Wu; I-Chen Harn; Ming-Jer Tang; Yi-Ting Chen; Fang-Chi Shen; Chien-Yi Lu; Tai-Chun Tsai; Jiunn-Jong Wu (Medical Microbiology and Immunology, 2013)

The impacts of coordinative exercise on executive function in kindergarten children: an ERP study - Yu-Kai Chang; Yu-Jung Tsai; Tai-Ting Chen; Tsung-Min Hung (Experimental Brain Research, 2013)

Non-coding RNAs in Alzheimer's Disease - Lin Tan; Jin-Tai Yu; Nan Hu; Lan Tan (Molecular Neurobiology, 2013)

De novo design of N-(pyridin-4-ylmethyl)aniline derivatives as KDR inhibitors: 3D-QSAR, molecular fragment replacement, protein-ligand interaction fingerprint, and ADMET prediction - Yanmin Zhang; Haichun Liu; Yu Jiao; Haoliang Yuan; Fengxiao Wang; Shuai Lu; Sihui Yao; Zhipeng Ke; Wenting Tai; Yulei Jiang; Yadong Chen; Tao Lu (Molecular Diversity, 2012)

Paternal deprivation alters play-fighting, serum corticosterone and the expression of hypothalamic vasopressin and oxytocin in juvenile male mandarin voles - Jianli Wang; Fadao Tai; Xingfu Yan; Peng Yu (Journal of Comparative Physiology A, 2012)

The Influence of Apolipoprotein E Epsilon4 Polymorphism on qEEG Profiles in Healthy Young Females: A Resting EEG Study - Tien-Wen Lee; Younger W.-Y. Yu; Chen-Jee Hong; Shih-Jen Tsai; Hung-Chi Wu; Tai-Jui Chen (Brain Topography, 2012)

Responses of bacterial and archaeal ammonia oxidisers of an acidic luvisols soil to different nitrogen fertilization rates after 9 years - Yong-gang Xu; Wan-tai Yu; Qiang Ma; Hua Zhou (Biology and Fertility of Soils, 2012)

Genetic Association of SLC2A14 Polymorphism with Alzheimer’s Disease in a Han Chinese Population - Wei Wang; Jin-Tai Yu; Wei Zhang; Wei-Zhen Cui; Zhong-Chen Wu; Qun Zhang; Lan Tan (Journal of Molecular Neuroscience, 2012)

Using coupled fish behavior–hydrodynamic model to investigate spawning migration of Japanese anchovy, Engraulis japonicus , from the East China Sea to Taiwan - CHEN‐YI TU; YU‐HENG TSENG; TAI‐SHENG CHIU; MAO‐LIN SHEN; CHIH‐HAO HSIEH (Fisheries Oceanography, 2012)
Adult Japanese anchovies ( Engraulis japonicus ) migrate from the East China Sea to the coastal region of Taiwan to spawn around late winter and early spring and, later, their larvae constitute important fisheries in Taiwan. However, their migration route and its mechanism remain unclear. To investigate their spawning migration, we used a coupled fish behavior–hydrodynamic modeling approach. The physical field is simulated by the Pacific Ocean adaptation of the TaIwan Multi‐scale Community Ocean Model (TIMCOM) and the fish migration by Lagrangian tracer tracking with the aid of approximation of fish swimming behavior. We investigated three fish behavioral scenarios: (i) passive tracking of the current, (ii) swimming along with the current, and (iii) swimming along with the current and then changing to swimming toward the optimal spawning temperature. The comparison with and without Changjiang discharge is used to investigate the impacts of discharge reduction due to the Three Gorges Dam. Our results suggest that spawning migration of Japanese anchovy from the East China Sea to Taiwan may be aided by the China Coastal Current and that adult anchovies cannot reach the spawning site by passive advection alone. Thus, the swimming behavior of anchovies is crucial during the spawning migration, as it provides extra velocity and the orientation to the favorable spawning grounds. In addition, the adult anchovy is unlikely to reach the coastal area of Taiwan without Changjiang discharge. Our findings indicate that a coupled fish behavior–hydrodynamic model can help understand the influences of physical environment on the migration of Japanese anchovies.

Characterization of the role of protein–cysteine residues in the binding with sodium arsenite - Yu-Ying Chang; Tai-Chih Kuo; Chun-Hua Hsu; Duen-Ren Hou; Yung-Hsi Kao; Rong-Nan Huang (Archives of Toxicology, 2012)

Oxidative stress in greater duckweed (Spirodela polyrhiza) caused by long-term NaCl exposure - In-Hwa Chang; Kai-Teng Cheng; Po-Chuan Huang; Yen-Yu Lin; Lee-Ju Cheng; Tai-Sheng Cheng (Acta Physiologiae Plantarum, 2012)

The Role of Clusterin in Alzheimer’s Disease: Pathways, Pathogenesis, and Therapy - Jin-Tai Yu; Lan Tan (Molecular Neurobiology, 2012)

The −1123G>C Variant of PTPN22 Gene Promoter is Associated with Latent Autoimmune Diabetes in Adult Chinese Hans - Fang Liu; Jiang Liu; Tai-shan Zheng; Qing Li; Chen Wang; Xiao-ping Pan; Huijuan Lu; Yu-wu Zhao (Cell Biochemistry and Biophysics, 2012)

Studies revealing bioremediation potential of the strain Burkholderia sp. GB-01 for abamectin contaminated soils - Shinawar Waseem Ali; Fang-bo Yu; Lian-tai Li; Xiao-hui Li; Li-feng Gu; Jian-dong Jiang; Shun-peng Li (World Journal of Microbiology and Biotechnology, 2012)

Knockdown of zinc finger protein, X-linked (ZFX) inhibits cell proliferation and induces apoptosis in human laryngeal squamous cell carcinoma - Jugao Fang; Zhenkun Yu; Meng Lian; Hongzhi Ma; Jun Tai; Luo Zhang; Demin Han (Molecular and Cellular Biochemistry, 2012)

Field balances and recycling rates of micronutrients with various fertilization treatments in Northeast China - Wan-Tai Yu; Hua Zhou; Xian-Jin Zhu; Yong-Gang Xu; Qiang Ma (Nutrient Cycling in Agroecosystems, 2011)

Sensitivity of tropical climate to low-level clouds in the NCEP climate forecast system - Zeng-Zhen Hu; Bohua Huang; Yu-Tai Hou; Wanqiu Wang; Fanglin Yang; Cristiana Stan; Edwin K. Schneider (Climate Dynamics, 2011)

Polyclonal rabbit anti-murine plasmacytoma cell globulins induce myeloma cells apoptosis and inhibit tumour growth in mice - Bo Mu; Jin-liang Yang; Lan-tu Gou; Yu-qin Yao; Yan Zhou; Zhi-hui Cheng; Hua-shan Shi; Zhi-yong Li; Yuan Wen; Fei Leng; Feng-yu Cui; Tian-tai Ma; et al. (Apoptosis, 2011)

Comparison of sociability, parental care and central estrogen receptor alpha expression between two populations of mandarin voles (Microtus mandarinus) - Ruiyong Wu; Aifang Yuan; Qinwei Yuan; Rui Guo; Fadao Tai; Zhenzhen Song; Chengjun Yu (Journal of Comparative Physiology A, 2011)

Lipopolysaccharide induces apoptotic insults to human alveolar epithelial A549 cells through reactive oxygen species-mediated activation of an intrinsic mitochondrion-dependent pathway - Chi-Yuan Chuang; Ta-Liang Chen; Yih-Giun Cherng; Yu-Tyng Tai; Tyng-Guey Chen; Ruei-Ming Chen (Archives of Toxicology, 2011)

Effects of fertilization on nutrient budget and nitrogen use efficiency of farmland soil under different precipitations in Northeastern China - Qiang Ma; Wan-Tai Yu; Shan-Min Shen; Hua Zhou; Zi-Shao Jiang; Yong-Gang Xu (Nutrient Cycling in Agroecosystems, 2010)

IL-6/STAT3/TFF3 signaling regulates human biliary epithelial cell migration and wound healing in vitro - Gui-xing Jiang; Xiang-yu Zhong; Yun-fu Cui; Wei Liu; Sheng Tai; Zhi-dong Wang; Yu-guang Shi; Shi-yong Zhao; Chun-long Li (Molecular Biology Reports, 2010)

The Removal of Ocular Artifacts from EEG Signals Using Adaptive Filters Based on Ocular Source Components - Hsiao-Lung Chan; Yu-Tai Tsai; Ling-Fu Meng; Tony Wu (Annals of Biomedical Engineering, 2010)

A new hexenol glycoside from leaves of Smallanthus sonchifolius - Xiang Zheng; Gai Kuo; Dou De-Qiang; Chen Gui-Rong; Kang Ting-Guo; Shi Yu-Yuan; Li Xing-Tai; Dong Feng (Natural Product Research, 2010)

Human herpesvirus 8 viral FLICE-inhibitory protein retards cell proliferation via downregulation of Id2 and Id3 expression - Yi-Fen Wang; Lin-Yu Wang; Yi-Ling Li; Huey-Wen Shyu; Yee-Hsuan Chiou; Miao-Chen Chou; Kuan-Hua Lin; Ming-Hong Tai; Chang-Yu Chen (Molecular and Cellular Biochemistry, 2010)

Mechanism of the Specific Neuronal Toxicity of a Type I Ribosome-Inactivating Protein, Trichosanthin - Ou Sha; David Tai-Wai Yew; Eric Yu-Pang Cho; Tzi-Bun Ng; Lin Yuan; Wing-Hang Kwong (Neurotoxicity Research, 2010)

Spatial and seasonal characterization of net primary productivity and climate variables in southeastern China using MODIS data - Dai-liang Peng; Jing-feng Huang; Alfredo R. Huete; Tai-ming Yang; Ping Gao; Yan-chun Chen; Hui Chen; Jun Li; Zhan-yu Liu (Journal of Zhejiang University-SCIENCE B, 2010)

Cold deep water in the South China Sea - Ya-Ting Chang; Wei-Lun Hsu; Jen-Hua Tai; Tswen Yung Tang; Ming-Huei Chang; Shenn-Yu Chao (Journal of Oceanography, 2010)

A new semi-dwarfing gene identified by molecular mapping of quantitative trait loci in barley - Guo Tai Yu; Richard D. Horsley; Bingxin Zhang; Jerome D. Franckowiak (Theoretical and Applied Genetics, 2010)

Plumbagin inhibits TPA-induced MMP-2 and u-PA expressions by reducing binding activities of NF-κB and AP-1 via ERK signaling pathway in A549 human lung cancer cells - Jiunn-Min Shieh; Tai-An Chiang; Wen-Teng Chang; Chang-Hung Chao; Yi-Chieh Lee; Guan-Yu Huang; You-Xin Shih; Yuan-Wei Shih (Molecular and Cellular Biochemistry, 2010)

Increase in intrathoracic volume in pectus excavatum patients after the Nuss procedure - Pei-Yeh Chang; Zhen-Yu Hsu; Jin-Yao Lai; Chao-Jan Wang; Yu-Tai Ching (Medical & Biological Engineering & Computing, 2010)

Effects of nutrient cycling on grain yields and potassium balance - Wan-Tai Yu; Zi-Shao Jiang; Hua Zhou; Qiang Ma (Nutrient Cycling in Agroecosystems, 2009)

Saturation and comparative mapping of the genomic region harboring Hessian fly resistance gene H26 in wheat - Guo Tai Yu; Xiwen Cai; Marion O. Harris; Yong Qiang Gu; Ming-Cheng Luo; Steven S. Xu (Theoretical and Applied Genetics, 2009)

Tissue expression of porcine FoxO1 and its negative regulation during primary preadipocyte differentiation - Wei-Jun Pang; Tai-Yong Yu; Liang Bai; Yan-Jun Yang; Gong-She Yang (Molecular Biology Reports, 2009)

Effect of calmidazolium on [Ca2+]i and viability in human hepatoma cells - Wei-Chuan Liao; Chorng-Chih Huang; He-Hsiung Cheng; Jue-Long Wang; Ko-Long Lin; Jin-Shiung Cheng; Kuo-Liang Chai; Pei-Te Hsu; Jeng-Yu Tsai; Yi-Chien Fang; Yih-Chau Lu; Hong-Tai Chang; et al. (Archives of Toxicology, 2009)

Surprisingly high orchid diversity in travertine and forest areas in the Huanglong valley, China, and implications for conservation - Bao-Qiang Huang; Xiao-Qin Yang; Fei-Hai Yu; Yi-Bo Luo; Yun-Dong Tai (Biodiversity and Conservation, 2008)

Infection of green fluorescence protein-tagged Fusarium graminearum on wheat and barley spikes - Xu Zhang; Theo Lee; Marie Dufresne; Tai-guo Liu; Wei-zhong Lu; Da-zhao Yu; Hong-xiang Ma (Cereal Research Communications, 2008)

Use of geochemical modeling to evaluate the hydraulic connection of aquifers: a case study from Chianan Plain, Taiwan - Hsueh-Yu Lu; Tsung-Kwei Liu; Wen-Fu Chen; Tsung-Ren Peng; Chung-Ho Wang; Meng-Hsun Tsai; Tai-Sheng Liou (Hydrogeology Journal, 2008)

Alteration of mitochondrial oxidative capacity during porcine preadipocyte differentiation and in response to leptin - Gui-Fen Luo; Tai-Yong Yu; Xu-Hui Wen; Ying Li; Gong-She Yang (Molecular and Cellular Biochemistry, 2007)

Identification of label-retaining cells in nasopharyngeal epithelia and nasopharyngeal carcinoma tissues - Hong-Bo Zhang; Cai-Ping Ren; Xu-Yu Yang; Lei Wang; Hui Li; Ming Zhao; Hong Yang; Kai-Tai Yao (Histochemistry and Cell Biology, 2007)

Production of high-content galacto-oligosaccharide by enzyme catalysis and fermentation with Kluyveromyces marxianus - Chao-Chun Cheng; Mei-Ching Yu; Tzu-Chien Cheng; Dey-Chyi Sheu; Kow-Jen Duan; Wei-Lun Tai (Biotechnology Letters, 2006)

Spatiotemporal Features of Severe Air Pollution in Northern Taiwan (8 pp) - Tai-Yi Yu; I-Cheng Chang (Environmental Science and Pollution Research, 2006)

Production of High-content Galacto-oligosaccharide by Enzyme Catalysis and Fermentation with Kluyveromyces marxianus - Chao-Chun Cheng; Mei-Ching Yu; Tzu-Chien Cheng; Dey-Chyi Sheu; Kow-Jen Duan; Wei-Lun Tai (Biotechnology Letters, 2006)

Effect of the Phosphate Group with Different Negative Charges on the Conformation of Phosphorylated Ser/Thr-Pro Motif - Yan-Ting Guo; Yan-Mei Li; Zhen-Tai Zhu; Yu-Fen Zhao (International Journal of Peptide Research and Therapeutics, 2005)

Expression of TRPC homologs in endothelial cells and smooth muscle layers of human arteries - Ham Yip; Wing-Yee Chan; Pan-Cheung Leung; Hiu-Yee Kwan; Cuiling Liu; Yu Huang; Villaz Michel; David Tai-Wai Yew; Xiaoqiang Yao (Histochemistry and Cell Biology, 2004)

Spatial and Temporal Features of Ambient Air-Quality over Taiwan - Tai-Yi Yu; Tai-Kuei Yu (Environmental Science and Pollution Research, 2004)

Expression of olfactory-type cyclic nucleotide-gated channel (CNGA2) in vascular tissues - Kwong-Tai Cheng; Franky Leung Chan; Yu Huang; Wing-Yee Chan; Xiaoqiang Yao (Histochemistry and Cell Biology, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Detection of the organophosphorus nerve agent sarin by a competitive inhibition enzyme immunoassay - Yong-xin Zhou; Qing-jin Yan; Yun-xiang Ci; Zhen-quan Guo; Kang -Tai Rong; Wen-bao Chang; Yu-fen Zhao (Archives of Toxicology, 1995)

On protein translocation across bacterial cytoplasmic membranes - Phang C. Tai; Jianping Lian; Nian-jun Yu; James Fandl; Haoda Xu; Jolanta Vidugiriene (Antonie van Leeuwenhoek, 1992)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)